Adhesive composition, adhesive sheet, optical laminate, and image display device
Patent Information
- Application Number
- CN202580022671.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-19
- Filing Date
- 2025-03-17
- Publication Date
- 2026-10-27
AI Technical Summary
[0027]根据本发明的实施方式,可以提供适于形成尽管为高折射率但可抑制相对于被粘附物的翘起、剥离的粘合片的粘合剂组合物。另外,可以提供由这样的粘合剂组合物形成的粘合片。进一步,可以提供具备这样的粘合片和光学膜的光学层叠体。进一步,可以提供具备这样的光学层叠体的图像显示装置。
Smart Images

Figure CN122996142A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to adhesive compositions, adhesive sheets, optical laminates, and image display devices. Background Technology
[0002] In recent years, image display devices, represented by liquid crystal displays and electroluminescent (EL) displays (e.g., organic EL displays and inorganic EL displays), have become increasingly widespread. Image display devices generally comprise an optical laminate containing optical substrates such as polarizing films and retardation films. In an optical laminate containing multiple optical substrates, a bonding layer is typically disposed between adjacent optical substrates to join them together. One example of a bonding layer is an adhesive sheet formed from an adhesive composition.
[0003] For improving the surface brightness of image display devices, it is advantageous to use adhesive sheets with high refractive index (see Patent Document 1). Patent Document 1 discloses a thermosetting adhesive composition comprising an acrylic polymer having a specific composition and weight-average molecular weight as a base polymer, and containing inorganic particles, plasticizers, and silane coupling agents.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-14376 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] According to the research of the inventors, when the refractive index of the adhesive sheet is increased, there is a tendency for the adhesive sheet to lift or peel off relative to the adhered object, especially in the display of portable devices such as smartphones.
[0009] The objective of this invention is to provide an adhesive composition suitable for forming an adhesive sheet that, despite having a high refractive index, can suppress lifting and peeling relative to the adhered object.
[0010] Problem Solving Methods
[0011] [1] The adhesive composition of the present invention comprises at least one selected from monomer component M and its polymer, wherein the monomer component M comprises monomer a having a double bond ring, the adhesive composition comprises an ultraviolet absorber, and the adhesive sheet formed from the adhesive composition has a refractive index of 1.55 or higher.
[0012] [2] In the adhesive composition described in [1] above, the double-bonded ring can be an aromatic ring. [3] In the adhesive composition described in [1] or [2] above, the monomer a may contain a (meth)acrylic acid monomer having the double bond ring described above.
[0013] [4] In any of the adhesive compositions described in [1] to [3] above, the monomer a may contain phenoxybenzyl acrylate.
[0014] [5] In any of the adhesive compositions described in [1] to [4] above, the content of monomer a in monomer component M may be 30% by weight or more.
[0015] [6] In any of the adhesive compositions described in [1] to [5] above, the ultraviolet absorber may be in a liquid state at 25°C.
[0016] [7] In any of the adhesive compositions described in [1] to [6] above, the haze of the adhesive sheet may be 2.0% or less.
[0017] [8] In any of the adhesive compositions described in [1] to [7] above, the transmittance of the adhesive sheet in the thickness direction is less than 25% for light with a wavelength of 380 nm and more than 80% for light with a wavelength of 420 nm.
[0018] [9] In any of the adhesive compositions described in [1] to [8] above, the color of the adhesive sheet may be in accordance with CIE1976 L as specified in JIS Z8781-4:2013. ,a ,b Color saturation in a color space The absolute value is represented as below 2.0.
[0019]
[10] The adhesive composition described in any one of [1] to [9] above may be a photocurable adhesive composition containing a photopolymerization initiator.
[0020]
[11] In the adhesive composition described in
[10] above, the photopolymerization initiator may be prepared at a concentration of 1×10 -4 The absorbance of a g / mL acetonitrile solution to light at a wavelength of 370 nm is 3 × 10⁻⁶ g / mL. -2 above.
[0021]
[12] In the adhesive composition described in
[10] or
[11] above, the residual amount of the photopolymerization initiator in the adhesive sheet may be less than 200 ppm (by weight).
[0022]
[13] The adhesive composition described in any one of [1] to
[12] above may further contain inorganic particles.
[0023]
[14] The adhesive sheet of the embodiment of the present invention is an adhesive sheet formed from the adhesive composition described in any one of [1] to
[13] above.
[0024]
[15] The optical laminate of the present invention comprises the adhesive sheet and the optical film described in
[14] above.
[0025]
[16] The image display device according to the embodiments of the present invention includes the optical laminate described above
[15] .
[0026] The effects of the invention
[0027] According to embodiments of the present invention, an adhesive composition suitable for forming an adhesive sheet that, despite having a high refractive index, can suppress lifting and peeling relative to the adhered object can be provided. Additionally, an adhesive sheet formed from such an adhesive composition can be provided. Furthermore, an optical laminate comprising such an adhesive sheet and an optical film can be provided. Further, an image display device comprising such an optical laminate can be provided. Attached Figure Description
[0028] Figure 1 This is a simplified cross-sectional view of an adhesive sheet according to one embodiment of the present invention.
[0029] Figure 2 This is a schematic diagram illustrating an example of a method for forming the adhesive sheet of the present invention from the adhesive composition of the present invention.
[0030] Figure 3 This is a simplified cross-sectional view of an optical laminate according to one embodiment of the present invention.
[0031] Figure 4 This is a simplified cross-sectional view of an optical laminate according to one embodiment of the present invention.
[0032] Figure 5 This is a simplified cross-sectional view of an optical laminate according to one embodiment of the present invention.
[0033] Figure 6 This is a simplified cross-sectional view of an optical laminate according to one embodiment of the present invention.
[0034] Figure 7 This is a simplified cross-sectional view of an optical laminate according to one embodiment of the present invention.
[0035] Figure 8 This is a simplified cross-sectional view of an image display device according to one embodiment of the present invention. Detailed Implementation
[0036] The present invention will now be described in detail, but the present invention is not limited to the following embodiments. Any modifications can be made to implement the invention without departing from the spirit of the invention.
[0037] [Terminology, etc.]
[0038] In this specification, the use of the term "weight" can be understood as "mass," which is the SI unit conventionally used to express weight. The reverse is also true.
[0039] In this specification, the term "(meth)acrylic acid" refers to "acrylic acid and / or methacrylic acid", the term "(meth)acrylate" refers to "acrylate and / or methacrylate", the term "(meth)allyl" refers to "allyl and / or methylallyl", and the term "(meth)acrolein" refers to "acrolein and / or methacrolein".
[0040] When the adhesive composition contains a polymer of monomer component M, the weight of the polymer is converted to the weight of each monomer before polymerization when calculating the proportion and content of the monomer.
[0041] 《1. Adhesive Composition》
[0042] The adhesive composition of the present invention (hereinafter referred to as "adhesive composition (A)") comprises at least one selected from monomer component M and its polymers. Monomer component M comprises monomer a having a double-bonded ring. Monomer a can help increase the refractive index of the adhesive sheet. The refractive index of the adhesive sheet formed by adhesive composition (A) is 1.55 or higher.
[0043] An example of adhesive composition (A) is a first composition comprising monomer component M. The first composition can be a photocurable adhesive composition. In the first composition, a portion of monomer component M can be formed as a partial polymer. The weight-average molecular weight of the partial polymer can be greater than 10,000, or greater than 20,000, greater than 20,000, greater than 30,000, greater than 30,000, greater than 40,000, greater than 50,000, greater than 75,000, and further greater than 100,000. Another example of adhesive composition (A) is a second composition comprising a base polymer comprising a polymer as monomer component M. The polymer as the base polymer has constituent units formed by the polymerization of monomer a. The second composition can be a thermocurable adhesive composition.
[0044] The adhesive composition (A) further comprises an ultraviolet absorber (hereinafter referred to as "UVA"). Monomer a, due to its absorption of light in the short wavelength range caused by its double-bonded ring, tends to have poor resistance to ultraviolet light compared to (meth)acrylic acid monomers that do not contain double-bonded rings. According to the researchers of the present invention, the aforementioned poor resistance of monomer a may affect peeling and flaking relative to the adhered object. UVA can help mitigate the effects of ultraviolet light on monomer a and the constituent units formed by the polymerization of monomer a.
[0045] The refractive index (hereinafter referred to as "refractive index n1") of the adhesive sheet formed by the adhesive composition (A) can be 1.56 or higher, 1.57 or higher, 1.58 or higher, 1.59 or higher, 1.60 or higher, 1.61 or higher, 1.62 or higher, 1.63 or higher, and further, 1.64 or higher. The upper limit of the refractive index n1 is, for example, 1.70 or lower, and can be 1.69 or lower, 1.68 or lower, 1.67 or lower, 1.66 or lower, 1.65 or lower, 1.64 or lower, 1.63 or lower, and further, 1.62 or lower. In this specification, the refractive index of the adhesive sheet refers to the refractive index of the adhesive sheet surface.
[0046] The refractive index of the adhesive sheet can be measured using a prism coupler at a measurement temperature of 25°C and a measurement wavelength of 594 nm. For adhesive sheets with a thickness less than 20 μm, measurements based on the light propagation mode are generally suitable. For adhesive sheets with a thickness greater than 20 μm, measurements based on the critical angle mode are generally suitable. A commercially available measuring device can be used, such as the Metricon 2010 / M prism coupler or its equivalent manufactured by Metricon Corporation. Specifically, the refractive index n1 of the photocurable adhesive composition can be evaluated according to the steps described in the examples (including the step of forming the adhesive sheet from the adhesive composition). For thermocurable adhesive compositions, the refractive index n1 can be evaluated using the following method: First, a release liner with a release layer on one side, as described in the examples, is prepared. Next, the adhesive composition to be evaluated is applied to the release layer of the release liner using an applicator to form a coating layer. Next, the entire assembly is heated at 130°C for 3 minutes to form an adhesive sheet with a thickness of 50 μm. The refractive index n1 is evaluated by using the exposed surface of the formed adhesive sheet as the evaluation surface.
[0047] 1-1. Monomer Component M
[0048] <1-1-a. Monomer a containing a double bond ring>
[0049] As described above, monomer component M contains monomer a having a double-bonded ring. Monomer component M may contain one or more monomers a. In this specification, a double-bonded ring means a ring in which at least one of the bonds constituting the ring is a double bond. Examples of double bonds include carbon-carbon double bonds, carbon-heteroatom double bonds, and heteroatom-heteroatom double bonds. Examples of heteroatoms include nitrogen, sulfur, and oxygen.
[0050] The number of double bonds in a double-bonded ring is not particularly limited, for example, it can be 1 to 10, or 2 to 5. When a double-bonded ring contains more than two double bonds, these double bonds can be conjugated or non-conjugated. The double-bonded ring is preferably an aromatic ring.
[0051] The double-bonded ring can be a carbon ring. Examples of carbon rings include benzene rings (which can be benzene rings that form part of biphenyl or fluorene structures), naphthalene rings, indene rings, azurite rings, anthracene rings, and phenanthrene rings. The double-bonded ring can be a heterocycle. Examples of heterocycles include pyridine rings, pyrimidine rings, pyrazine rings, triazine rings, pyrrole rings, pyrazole rings, imidazole rings, triazole rings, thiazole rings, isothiazole rings, thiazole rings, and thiophene rings. Examples of heteroatoms that can be included in the heterocycle as cyclizing atoms are at least one selected from nitrogen, sulfur, and oxygen. The heteroatom can be one or both of nitrogen and sulfur. The double-bonded ring can be a fused ring. An example of monomer a is a structure like the dinaphthothiophene structure, which has one or more carbon rings fused with one or more heterocycles.
[0052] The double-bonded ring may have one or more substituents (except for the olefinic unsaturated groups described later) on the cyclizing atom, or it may not have substituents. Examples of substituents are alkyl, alkoxy, aryloxy, hydroxyl, halogen atoms (fluorine, chlorine, bromine, etc.), hydroxyalkyl, hydroxyalkoxy, and glycidoxy. However, the substituents are not limited to the above examples. The substituent may contain carbon atoms, in which case the number of carbon atoms contained in the substituent may be, for example, 1 to 4, 1 to 3, or even 1 to 2. One example of a double-bonded ring is that the cyclizing atom does not have a substituent. Another example of a double-bonded ring is that the cyclizing atom has one or more substituents selected from alkyl, alkoxy, and halogen atoms (e.g., bromine).
[0053] In monomer a, the number of double-bonded rings contained in one molecule can be, for example, 1, or more than 2. There is no particular upper limit to the number of double-bonded rings, for example, 16 or less. The upper limit can be less than 12, less than 8, less than 6, less than 5, less than 4, less than 3, and further less than 2.
[0054] In monomer a, the double-bonded ring is preferably located on the side chain. In other words, monomer a preferably has at least one double-bonded ring and at least one olefinically unsaturated group in one molecule. Monomer a can be a monomer (aromatic ring monomer) having at least one aromatic ring and at least one olefinically unsaturated group in one molecule. As monomer a, it is preferable to use a compound that contains one olefinically unsaturated group in one molecule (in other words, a monofunctional monomer).
[0055] Examples of olefinically unsaturated groups are (meth)acryloyl, vinyl, and (meth)allyl. From the viewpoint of polymerization reactivity, (meth)acryloyl is preferred, and from the viewpoint of flexibility and adhesion, acryloyl is more preferred. In other words, monomer a preferably comprises a (meth)acrylic acid monomer having a double-bonded ring, and more preferably comprises an acrylic acid monomer having a double-bonded ring. Examples of (meth)acrylic acid monomers having a double-bonded ring include, for example, aromatic ring (meth)acrylates. Specific examples of aromatic ring (meth)acrylates will be described later.
[0056] The double-bonded ring and the olefinic unsaturated group can be directly bonded or bonded via a linking group. An example of the linking group includes one or more of the following: alkylene, oxoalkylene, poly(olefinic oxide), phenyl, alkylphenyl, alkoxyphenyl, groups formed by replacing one or more hydrogen atoms of these groups with hydroxyl groups (e.g., hydroxyalkylene), oxy (-O-), and thiooxy (-S-). In one example of monomer a, the double-bonded ring and the olefinic unsaturated group are directly bonded together. In another example of monomer a, the double-bonded ring and the olefinic unsaturated group are bonded together via a linking group selected from alkylene, oxoalkylene, and poly(olefinic oxide). The number of carbon atoms in the alkylene and oxoalkylene groups that may be included in the linking group is, for example, 1 to 4, 1 to 3, and further, 1 to 2. The number of repetitions of the olefinic oxide unit in the poly(olefinic oxide) group that may be included in the linking group is, for example, 1 to 8, 1 to 6, 1 to 4, 1 to 3, 2 to 3, further, 1 to 2, or 2, or even 1.
[0057] Specific examples of monomer a are aromatic ring (meth)acrylates and aromatic ring vinyl compounds. One or more aromatic ring (meth)acrylates and aromatic ring vinyl compounds may be used.
[0058] Monomer a can contain two or more aromatic rings (preferably carbocyclic rings) in one molecule. Monomers having two or more aromatic rings and at least one olefinic unsaturated group in one molecule (monomers containing multiple aromatic rings) are particularly suitable for increasing the refractive index of adhesive sheets.
[0059] Examples of monomers containing multiple aromatic rings include: monomers having a structure in which two or more non-fused aromatic rings are bonded together via a linking group; monomers having a structure in which two or more non-fused aromatic rings are directly bonded together; monomers having fused rings; monomers having a fluorene structure; monomers having a dinaphthothiophene structure; and monomers having a dibenzothiophene structure. Among these, monomers having a structure in which two or more non-fused aromatic rings are bonded together via a linking group (e.g., phenoxybenzyl (meth)acrylate described later) are preferred.
[0060] The linking group can contain atoms such as P, Ge, Te, Se, N, S, and Si, which can bond to oxygen atoms. However, the linking group may also not contain any of these atoms. Examples of linking groups are oxygen groups (-O-), thiooxy groups (-S-), and oxoalkylene groups (e.g., -O-(CH2)). n -; n is 1~3, preferably 1), thionyl groups (e.g., -S-(CH2) n -; n is 1~3, preferably 1), straight-chain alkylene (-(CH2) n -; n is 1 to 6, preferably 1 to 3), and the group formed by partial or complete halogenation of the above-mentioned oxyalkylene, thioalkylene, and straight-chain alkylene groups. The linking group may include one or more selected from oxy, thiooxy, oxyalkylene, and straight-chain alkylene groups. Specific examples of monomers having a structure in which two or more non-fused aromatic rings are bonded by a linking group are (meth)acrylate phenoxybenzyl ester, (meth)acrylate thiophenoxybenzyl ester, and (meth)acrylate benzyl benzyl ester.
[0061] Examples of monomers having a structure formed by the direct bonding of two or more non-fused aromatic rings include (meth)acrylates containing a biphenyl structure, (meth)acrylates containing a triphenyl structure, and monomers containing vinylbiphenyl. Specific examples are o-phenylphenol (meth)acrylate, biphenyl methyl (meth)acrylate, and biphenyl methyl (meth)acrylate.
[0062] Examples of monomers with fused rings include naphthyl ring (meth)acrylates, anthracene ring (meth)acrylates, acetylnaphthalene, and acetylanthracene. Specific examples include 1-naphthyl methyl (meth)acrylate (also known as 1-naphthyl methyl (meth)acrylate), hydroxyethylated β-naphthol acrylate, 2-naphthyl ethyl (meth)acrylate, 2-naphthoxyethyl acrylate, and 2-(4-methoxy-1-naphthoxy)ethyl (meth)acrylate.
[0063] Examples of monomers having a fluorene structure are 9,9-bis(4-hydroxyphenyl)fluorene(meth)acrylate and 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene(meth)acrylate. It should be noted that monomers having a fluorene structure are included in the concept of monomers having structures formed by the direct bonding of two benzene rings, since they possess a structure formed by the direct bonding of two or more non-fused aromatic rings.
[0064] Examples of monomers having a dinaphthothiophene structure are dinaphthothiophene containing a (meth)acryloyl group, dinaphthothiophene containing an acetyl group, and dinaphthothiophene containing a (meth)allyl group. Specific examples include (meth)acryloyloxymethyl dinaphthothiophene (e.g., a compound having a structure in which a CH2CH(R1)C(O)OCH2 group is bonded at the 5 or 6 position of the dinaphthothiophene ring; R1 being a hydrogen atom or a methyl group), (meth)acryloyloxyethyl dinaphthothiophene (e.g., a compound having a CH2CH(R1)C(O)OCH(CH3) group or a CH2CH(R1)C(O)OCH2CH2 group is bonded at the 5 or 6 position of the dinaphthothiophene ring; R1 being a hydrogen atom or a methyl group), vinyl dinaphthothiophene (e.g., a compound having a structure in which a vinyl group is bonded at the 5 or 6 position of the dinaphthothiophene ring), and (meth)allyloxy dinaphthothiophene. It should be noted that monomers with a dinaphthothiophene structure are included in the concept of monomers with fused rings because they have a naphthalene structure, and also because they have a structure formed by the fusion of a thiophene ring and two naphthalene structures.
[0065] Examples of monomers having a dibenzothiophene structure include dibenzothiophene containing a (meth)acryloyl group and dibenzothiophene containing an acetyl group. It should be noted that monomers having a dibenzothiophene structure are included in the concept of monomers with fused rings because they possess a structure formed by the fusion of a thiophene ring and two benzene rings. Neither dinaphthothiophene nor dibenzothiophene structures belong to structures formed by the direct bonding of two or more non-fused aromatic rings.
[0066] Monomer a can be a monomer (containing a single aromatic ring monomer) having an aromatic ring (preferably a carbocyclic ring) and at least one olefinic unsaturated group in one molecule.
[0067] Examples of monomers containing a single aromatic ring include benzyl (meth)acrylate, methoxybenzyl (meth)acrylate, phenyl (meth)acrylate, ethoxylated phenol (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxybutyl (meth)acrylate, cresol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, benzyl chloro (meth)acrylate, and other (meth)acrylates containing a carbon aromatic ring; 2-(4,6-dibromo-2-sec-butylphenoxy)ethyl (meth)acrylate, 2-(4,6-dibromo-2-isopropylphenoxy)ethyl (meth)acrylate, and (meth)acrylate 6-(4,6-dibromo-2-sec-butylphenoxy)hexyl ester, 6-(4,6-dibromo-2-isopropylphenoxy)hexyl acrylate, 2,6-dibromo-4-nonylphenyl acrylate, 2,6-dibromo-4-dodecylphenyl acrylate, and other (meth)acrylates containing bromine-substituted aromatic rings; vinyl compounds containing carbon aromatic rings such as styrene, α-methylstyrene, vinyltoluene, and tert-butylstyrene; and compounds with vinyl substituents on heteroaromatic rings such as N-vinylpyridine, N-vinylpyrimidine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazolium, and N-vinylpyrazole.
[0068] Monomer a can have a structure in which an oxyethylene chain is sandwiched between the olefinic unsaturated group and the double-bonded ring in the various monomers a described above. Monomers having this structure can be considered ethoxylated versions of the original monomer. The number of repetitions of the oxyethylene unit (-CH2CH2O-) in the oxyethylene chain is, for example, 1 to 8, but can be 1 to 6, 1 to 4, 1 to 3, further 1 to 2, or even 1. Examples of monomers a as ethoxylated compounds are ethoxylated o-phenylphenol (meth)acrylate, ethoxylated nonylphenol (meth)acrylate, ethoxylated cresol (meth)acrylate, phenoxyethyl (meth)acrylate, and phenoxydiethylene glycol (meth)acrylate.
[0069] The proportion of monomers containing multiple aromatic rings in monomer a is not particularly limited, and can be 5% by weight or more, 25% by weight or more, and further, 40% by weight or more. From the viewpoint of further improving the refractive index of the adhesive sheet, the above proportion can be 50% by weight or more, exceeding 50% by weight, 60% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, and further, 98% by weight or more. Monomer a can be substantially 100% by weight of monomers containing multiple aromatic rings. In other words, monomer a can use only one or more monomers containing multiple aromatic rings. The upper limit of the above proportion is not particularly limited, and can be less than 100% by weight, 98% by weight or less, 97% by weight or less, 96% by weight or less, and further, 95% by weight or less.
[0070] The proportion of monomers containing multiple aromatic rings in monomer component M is not particularly limited, and can be 3% by weight or more, 10% by weight or more, and further, 25% by weight or more. From the viewpoint of improving the refractive index of the adhesive sheet, the above proportions can exceed 35% by weight, exceed 50% by weight, exceed 60% by weight, and be 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, exceed 90% by weight, and further, 95% by weight or more. The upper limit of the above proportions is not particularly limited, and can be less than 100% by weight, 98% by weight or less, 97% by weight or less, 96% by weight or less, and further, 95% by weight or less.
[0071] Monomer A may include high-refractive-index monomers. In this specification, a high-refractive-index monomer refers to a monomer having a refractive index of 1.51 or higher, 1.53 or higher, 1.55 or higher, 1.56 or higher, 1.57 or higher, 1.58 or higher, 1.59 or higher, 1.60 or higher, 1.61 or higher, 1.62 or higher, 1.63 or higher, 1.64 or higher, 1.65 or higher, 1.66 or higher, 1.67 or higher, 1.68 or higher, and further, 1.69 or higher. There is no particular upper limit to the refractive index of the high-refractive-index monomer; for example, it can be below 3.00, below 2.50, below 2.00, below 1.90, below 1.80, and further, below 1.70. A single high-refractive-index monomer may be used, or two or more may be used in combination.
[0072] The refractive index of the monomer can be measured using an Abbe refractometer at a measurement wavelength of 589 nm and a measurement temperature of 25°C. An Abbe refractometer, such as the ATAGO DR-M4 or its equivalent (e.g., DR-M2), can be used. If the monomer manufacturer provides a nominal value for the refractive index at 25°C, that value can be used as the refractive index.
[0073] Examples of high refractive index monomers include phenoxybenzyl acrylate (refractive index 1.566), 1-naphthyl methyl acrylate (refractive index 1.595), ethoxylated o-phenylphenol acrylate (refractive index 1.578 when the repeat number of the oxyethylidene unit is 1), benzyl acrylate (refractive index 1.519), phenoxyethyl acrylate (refractive index 1.517), phenoxydiethylene glycol acrylate (refractive index 1.510), 6-acryloyloxymethyl dinaphthothiophene (refractive index 1.75), 6-methacryloyloxymethyl dinaphthothiophene (refractive index 1.726), 5-acryloyloxyethyl dinaphthothiophene (refractive index 1.786), 6-acryloyloxyethyl dinaphthothiophene (refractive index 1.722), and 6-vinyl dinaphthothiophene (refractive index 1.802) and 5-vinyl dinaphthothiophene (refractive index 1.793). However, high refractive index monomers are not limited to the examples mentioned above.
[0074] There is no particular limitation on the proportion of high-refractive-index monomers in monomer a, for example, it can be 5% by weight or more, or 25% by weight or more, 35% by weight or more, or even 40% by weight or more. From the viewpoint of further increasing the refractive index of the adhesive sheet, the above proportions can be 50% by weight or more, 70% by weight or more, 85% by weight or more, 90% by weight or more, or even 95% by weight or more. In monomer composition M, only high-refractive-index monomers can be included as monomer a. The upper limit of the above proportions can be less than 100% by weight, or 98% by weight or less, 97% by weight or less, 96% by weight or less, or even 95% by weight or less.
[0075] There is no particular limitation on the proportion of high-refractive-index monomers in monomer component M; it can be 3% or more by weight, 10% or more by weight, 25% or more by weight, and even more than 35% by weight. From the viewpoint of increasing the refractive index of the adhesive sheet, the above proportions can exceed 50% by weight, exceed 60% by weight, be 70% or more by weight, 75% or more by weight, 80% or more by weight, 85% or more by weight, 90% or more by weight, exceed 90% by weight, be 95% or more by weight, and even more than 100% by weight. There is no particular limitation on the upper limit of the above proportions; it can be less than 100% by weight, less than 98% by weight, less than 97% by weight, less than 96% by weight, and even less than 95% by weight.
[0076] Monomer a may contain a low-Tg monomer whose Tg (hereinafter referred to as "monomer Tg") when forming a homopolymer is below 10°C. The Tg of the low-Tg monomer may be, for example, below 5°C, below 0°C, below -10°C, below -20°C, below -25°C, or even below -30°C. There is no particular limitation on the lower limit of the Tg of the low-Tg monomer; for example, it may be above -70°C, above -55°C, or even above -45°C. A single low-Tg monomer may be used, or two or more may be used in combination.
[0077] Examples of low Tg monomers are phenoxybenzyl acrylate (Tg: -35℃), benzyl acrylate (Tg: 6℃), phenoxyethyl acrylate (Tg: 2℃), and phenoxydiethylene glycol acrylate (Tg: -35℃).
[0078] There is no particular limitation on the proportion of low-Tg monomers in monomer a, for example, it can be 5% by weight or more, or 25% by weight or more, 40% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, 75% by weight or more, 85% by weight or more, 90% by weight or more, and further, 95% by weight or more. In monomer component M, it may contain only low-Tg monomers as monomer a. The upper limit of the above proportions can be less than 100% by weight, less than 98% by weight, less than 97% by weight, less than 96% by weight, and further, less than 95% by weight.
[0079] There is no particular limitation on the proportion of low-Tg monomers in monomer component M, which can be 3% or more by weight, 10% or more by weight, 25% or more by weight, and even more than 35% by weight. From the viewpoint of improving the refractive index of the adhesive sheet, the above proportions can exceed 50% by weight, exceed 60% by weight, be 70% or more by weight, 75% or more by weight, 80% or more by weight, 85% or more by weight, 90% or more by weight, exceed 90% by weight, be 95% or more by weight, and even more than 100% by weight. There is no particular limitation on the upper limit of the above proportions, which can be less than 100% by weight, less than 98% by weight, less than 97% by weight, less than 96% by weight, and even less than 95% by weight.
[0080] As monomer a, low-Tg monomers and high-Tg monomers can be combined and included in monomer component M. The Tg of the high-Tg monomer exceeds 10°C, can exceed 15°C, and can even exceed 20°C.
[0081] Monomer a may contain phenoxybenzyl acrylate. Phenoxybenzyl acrylate is particularly suitable for balancing the refractive index and adhesive properties of adhesive sheets due to its refractive index and Tg.
[0082] Monomer a can also be selected from compounds that do not have a structure formed by direct bonding of two or more non-fused aromatic rings (e.g., biphenyl structure). The proportion of compounds in monomer a that have a structure formed by direct bonding of two or more non-fused aromatic rings can be less than 5% by weight, less than 3% by weight, or even 0% by weight.
[0083] The content of monomer a in monomer component M is, for example, 30% by weight or more, and can be 50% by weight or more, 60% by weight or more, 70% by weight or more, exceeding 70% by weight, 75% by weight or more, 80% by weight or more, 85% by weight or more, 87% by weight or more, 90% by weight or more, 92% by weight or more, 93% by weight or more, 94% by weight or more, and further can be 95% by weight or more. The upper limit of the above content is, for example, 100% by weight, and can be 98% by weight or less, 97% by weight or less, 96% by weight or less, 95% by weight or less, 93% by weight or less, 90% by weight or less, less than 90% by weight, 85% by weight or less, 80% by weight or less, 75% by weight or less, 70% by weight or less, 60% by weight or less, 50% by weight or less, 25% by weight or less, 10% by weight or less, and further can be 5% by weight or less.
[0084] <1-1-b. Other monomers>
[0085] Monomer component M may contain monomers other than monomer a mentioned above. An example of other monomers is a hydroxyl-containing monomer. A hydroxyl-containing monomer has at least one hydroxyl group and at least one olefinically unsaturated group in one molecule. Monomer component M may contain one or more hydroxyl-containing monomers.
[0086] Examples of olefinic unsaturated groups are the same as those described above in the description of monomer a. Hydroxyl-containing monomers can be (meth)acrylic acid monomers.
[0087] Examples of hydroxyl-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylaurate (meth)acrylate, and methyl (4-hydroxymethylcyclohexyl)acrylate. The preferred hydroxyl-containing monomers are 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate. The content of the hydroxyl-containing monomer in monomer component M is, for example, 25% by weight or less, and can be 20% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, and further, 2% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. Monomer component M may also not contain hydroxyl-containing monomers. It should be noted that in the calculation of the content of monomer component M, monomers containing double-bonded rings and hydroxyl groups are treated as monomer a.
[0088] Another example of a monomer that can be included in monomer component M is an alkyl (meth)acrylate having an alkyl group having 1 to 20 carbon atoms in its side chain. The alkyl group may have 7 or fewer carbon atoms, 6 or fewer, 5 or fewer, or even 4 or fewer. The alkyl group may be linear or branched. Examples of alkyl methacrylates are methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, isoheptyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, isooctyl methacrylate, n-nonyl methacrylate, isononyl methacrylate, n-decyl methacrylate, isodecyl methacrylate, n-dodecyl methacrylate (laurate methacrylate), n-tridecyl methacrylate, n-tetradecyl methacrylate, n-pentadecanyl methacrylate, n-hexadecyl methacrylate, hexadecyl methacrylate, heptadecanyl methacrylate, and octadecyl methacrylate. Alkyl methacrylates can be n-butyl methacrylates.
[0089] The content of alkyl (meth)acrylate in monomer component M is, for example, 25% by weight or less, and can be 20% by weight or less, 15% by weight or less, 10% by weight or less, 7% by weight or less, 5% by weight or less, and further, 4% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. Monomer component M may also not contain alkyl (meth)acrylate.
[0090] Another example of a monomer that can be included in monomer component M is an aliphatic ring monomer. An aliphatic ring monomer has at least one aliphatic ring and at least one olefinically unsaturated group in one molecule. It should be noted that aliphatic ring monomers can be used alone or in combination of two or more.
[0091] Examples of olefinic unsaturated groups are the same as those described above in the description of monomer a. Monomers containing aliphatic rings can be (meth)acrylic acid monomers.
[0092] Examples of aliphatic ring monomers include: cyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, cyclooctyl methacrylate, isobornyl methacrylate, dicyclopentyl methacrylate, dicyclopentoxyethyl methacrylate, tricyclopentyl methacrylate, and adamantyl methacrylate.
[0093] The content of aliphatic ring monomers in monomer component M is, for example, 25% by weight or less, and can be 20% by weight or less, 15% by weight or less, 10% by weight or less, 7% by weight or less, 5% by weight or less, and further, 4% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. Monomer component M may also not contain aliphatic ring monomers.
[0094] Another example of a monomer that can be included in monomer component M is a carboxyl-containing monomer. A carboxyl-containing monomer that may be included in monomer component M has at least one carboxyl group and at least one olefinically unsaturated group in one molecule. Monomer component M may contain one or more carboxyl-containing monomers.
[0095] Examples of olefinic unsaturated groups are the same as those described above in the description of monomer a. The carboxyl-containing monomer can be a (meth)acrylic acid monomer.
[0096] Examples of carboxyl-containing monomers include (meth)acrylic acid, carboxyethyl (meth)acrylic acid, carboxypentyl (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid. The content of carboxyl-containing monomers in monomer component M is, for example, 10% by weight or less, but can be 7% by weight or less, 5% by weight or less, 3% by weight or less, and further, 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, but can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. Monomer component M may also not contain carboxyl-containing monomers. It should be noted that in the calculation of the content in monomer component M, monomers containing double-bonded rings and carboxyl groups are treated as monomer a.
[0097] Monomer component M may contain monomers other than those mentioned above.
[0098] 1-2. UVA
[0099] Examples of UVA include triazine UVA, benzotriazole UVA, benzophenone UVA, hydroxybenzophenone UVA, salicylate UVA, and cyanoacrylate UVA. Each UVA is a compound having a triazine skeleton, a benzotriazole skeleton, a benzophenone skeleton, a hydroxybenzophenone skeleton, a salicylate structure, or a cyanoacrylate structure. UVA is preferably a triazine or benzotriazole UVA, more preferably a benzotriazole UVA.
[0100] Examples of triazine UVA derivatives include 2,4-bis[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (Tinosorb S, manufactured by BASF) and 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (TINUVIN). 460 (BASF manufactured), the reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hydroxyphenyl with [(C10-C16 (mainly C12-C13)alkoxy)methyl]ethylene oxide (TINUVIN400, BASF manufactured), 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol, 2-(2,4-dihydroxyphenyl)-5-[(2,4-dihydroxyphenyl)-5-[(2,4-dimethyl ... The reaction products of 2-(4,6-diphenyl-1,3,5-triazine and (2-ethylhexyl)-epoxypropionate (TINUVIN 405, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]phenol (TINUVIN 1577, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol (ADK STAB LA46, manufactured by ADEKA), and 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (TINUVIN 479, manufactured by BASF).
[0101] Examples of benzotriazole UVA are 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF) and 2-(2H-1,2,3-benzotriazole-2-yl)-6-dodecyl-4-methylphenol (TINUVIN 928). 571, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVINPS, manufactured by BASF), esters of phenylpropionic acid and 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy (C7-9 side chain and straight-chain alkyl) (TINUVIN384-2, manufactured by BASF), 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN900, manufactured by BASF), reaction product of methyl 3-(3-(2H-benzotriazole-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 (TINUVIN1130, manufactured by BASF), 2-(2H-benzotriazole-2-yl)-p-cresol (TINUVIN P, manufactured by BASF), 2(2H-benzotriazol-2-yl)-4-6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN234, manufactured by BASF), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN326, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (TINUVIN328, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol ( TINUVIN 329 (manufactured by BASF), the reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate and polyethylene glycol 300 (TINUVIN 213 (manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (TINUVIN 571 (manufactured by BASF), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidemethyl)-5-methylphenyl]benzotriazole (Sumisorb 250 (manufactured by Sumitomo Chemical Industry)).
[0102] UVA can be in a liquid state at 25°C. Being in a liquid state at 25°C helps to suppress UVA precipitation in adhesive sheets formed from adhesive composition (A), such as precipitation during storage of the adhesive sheet.
[0103] UVA can be benzotriazole UVA, which is liquid at 25°C.
[0104] The adhesive composition (A) may contain one or more UVA.
[0105] The UVA content in the adhesive composition (A) relative to 100 parts by weight of the monomer component M and its polymer is, for example, 0.1 parts by weight or more, and may be 0.2 parts by weight or more, 0.3 parts by weight or more, 0.4 parts by weight or more, 0.5 parts by weight or more, 0.6 parts by weight or more, 0.7 parts by weight or more, 0.8 parts by weight or more, 0.9 parts by weight or more, 1.0 parts by weight or more, 1.1 parts by weight or more, 1.2 parts by weight or more, 1.3 parts by weight or more, 1.5 parts by weight or more, 1.8 parts by weight or more, 2.0 parts by weight or more, 2.5 parts by weight or more, and further may be 3.0 parts by weight or more. There is no particular upper limit to the above content; for example, it may be 10.0 parts by weight or less, or 8.0 parts by weight or less, 6.0 parts by weight or less, and further may be 5.0 parts by weight or less.
[0106] 1-3. Characteristics
[0107] <1-3-1. Haze>
[0108] The haze of the adhesive sheet formed from the adhesive composition (A) can be 2.0% or less. The haze can be 1.7% or less, 1.5% or less, 1.2% or less, 1.0% or less, 0.9% or less, 0.8% or less, and further, 0.7% or less. The lower limit of the haze is not particularly limited and can be 0.1% or more. Adhesive compositions capable of forming low-haze adhesive sheets are particularly suitable for forming adhesive sheets in optical laminates.
[0109] In this specification, the haze of the adhesive sheet refers to the ratio of diffused transmitted light to total transmitted light when visible light is irradiated onto a 50 μm thick adhesive sheet, which is the object of the test. The haze can be calculated using the following formula: Th is the haze (%), Td is the scattered light transmittance, and Tt is the total light transmittance. It can be evaluated using a commercially available haze meter. Regarding photocurable adhesive compositions, the aforementioned haze, as a characteristic of the adhesive composition, can be specifically evaluated using the steps described in the examples (including the step of forming the adhesive sheet from the adhesive composition). Regarding thermocurable adhesive compositions, an adhesive sheet formed using the same method as the adhesive sheet used in the determination of refractive index n1 can be used as a test sample for evaluation.
[0110] Formula: Th(%)=(Td / Tt)×100
[0111] It can be: the adhesive composition (A) contains UVA that is liquid at 25°C, and the haze of the adhesive sheet formed by the adhesive composition (A) is less than 2.0% or within the range mentioned above.
[0112] <1-3-2. Light transmittance>
[0113] The transmittance in the thickness direction of the adhesive sheet formed by the adhesive composition (A) can be less than 25% for light with a wavelength of 380 nm and more than 80% for light with a wavelength of 420 nm. The transmittance for light with a wavelength of 380 nm can be less than 20%, less than 18%, less than 16%, less than 15%, less than 13%, less than 11%, less than 10%, less than 9%, less than 7%, less than 5%, less than 4%, less than 2%, and further less than 1%. The lower limit of this transmittance is 0%. The transmittance for light with a wavelength of 420 nm can be more than 82%, more than 84%, more than 85%, more than 87%, more than 88%, and further more than 90%. The upper limit of this transmittance is not particularly limited and can be less than 95%. Suppressing the transmittance for light with a wavelength of 380 nm helps to improve the UV resistance of the adhesive sheet.
[0114] The transmittance in the thickness direction of the adhesive sheet can be evaluated using a commercially available transmittance meter. For photocurable adhesive compositions, the aforementioned transmittance, a characteristic of the adhesive composition, can be specifically evaluated using the steps described in the examples (including the step of forming the adhesive sheet from the adhesive composition). For thermocurable adhesive compositions, the adhesive sheet formed using the same method as the adhesive sheet used in the determination of refractive index n1 can be used as the sample for evaluation.
[0115] <1-3-3. Chromaticity>
[0116] The color of the adhesive sheet formed from the adhesive composition (A) conforms to CIE 1976 L as specified in Japanese Industrial Standard (JIS) Z8781-4:2013. ,a ,b Color saturation in a color space The absolute value can be below 2.0. (Chromaticity) A low absolute value means that yellowing and other coloration are suppressed. (Chromaticity) The absolute value can be below 1.7, below 1.5, below 1.2, below 1.0, below 0.9, below 0.8, and even below 0.7. (Colorimetry) The lower limit of the absolute value is 0, and it can be greater than 0.1.
[0117] Color of adhesive sheet The evaluation can be performed using a commercially available colorimeter capable of measurements based on JIS Z8781-4:2013. Regarding the photocurable adhesive composition, the aforementioned colorimetric properties are characteristics of the adhesive composition. Specifically, the evaluation can be performed using the steps described in the examples (including the step of forming an adhesive sheet from the adhesive composition). For thermosetting adhesive compositions, an adhesive sheet formed using the same method as the adhesive sheet used in the determination of refractive index n1 can be used as a sample for evaluation.
[0118] The adhesive sheet formed from the adhesive composition (A) can have two or more properties selected from the above-mentioned haze, light transmittance and colorimetry in any combination.
[0119] 1-4. Curing Type
[0120] <1-4-1. Light-curing type>
[0121] The adhesive composition (A) can be a photocurable adhesive composition containing a photopolymerization initiator. It should be noted that, compared with thermocurable adhesives that mainly utilize heat to form the adhesive sheet, photocurable compositions can suppress the energy necessary for the formation of the adhesive sheet, and therefore are particularly preferred for the purposes of environmental protection and sustainability.
[0122] The components that may be included in a light-curing adhesive composition (A) are described.
[0123] The photopolymerization initiator that may be included in the photocurable adhesive composition (A) may be a photoradical generator that generates free radicals by visible light and / or ultraviolet light with wavelengths shorter than 450 nm.
[0124] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzoin dimethyl ether; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkyl acetophenones such as 1-hydroxycyclohexylphenyl ketone; substituted α-alcohol ketones such as 2-methyl-2-hydroxyphenylacetophenone; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; and 1-phenyl... Photoactive oximes such as -1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone and other benzophenone compounds; thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone Thioxanone compounds such as isopropyl thioxanone, 2,4-diisopropyl thioxanone, and 2,4-diethyl thioxanone; 2,4,6-trichloro-triazine, 2-phenyl-4,6-bis(trichloromethyl)-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-triazine, and 2-piperyl-4,6-bis(trichloromethyl)-triazine. Triazine compounds, including 2,4-bis(trichloromethyl)-6-styryl-triazine, 2-(naphthyl-1-yl)-4,6-bis(trichloromethyl)-triazine, 2-(4-methoxy-naphthyl-1-yl)-4,6-bis(trichloromethyl)-triazine, 2,4-trichloromethyl-(piperyl)-6-triazine, and 2,4-trichloromethyl-(4'-methoxystyryl)-6-triazine; 1,2-octanedione, Oxime esters such as 1-[4-(phenylthio)-, 2-(O-benzoyl oxime)] and O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethoxy)hydroxylamine; phosphine compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyl diphenylphosphine oxide; quinone compounds such as 9,10-phenanthroquinone, camphorquinone, and ethylanthraquinone; borate esters; carbazole compounds; imidazole compounds; and titanium dioxide compounds. The photocurable adhesive composition (A) may contain one or more photopolymerization initiators.
[0125] Specific examples of photopolymerization initiators include 2,2-dimethoxy-1,2-diphenylethane-1-one (Omnirad 651, manufactured by IGM Resins) and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad 819, manufactured by IGM Resins). However, the photopolymerization initiators that may be included in the photocurable adhesive composition (A) are not limited to the above examples.
[0126] Photopolymerization initiator at a concentration of 1×10-4 The absorbance of a g / mL acetonitrile solution for light at a wavelength of 370 nm is 3 × 10⁻⁶ g / mL. -2 above.
[0127] The residual amount of photopolymerization initiator in the adhesive sheet formed from adhesive composition (A) can be 200 ppm (weight basis; the same below) or less. Furthermore, for the adhesive sheet formed from adhesive composition (A), when a concentration of 1×10⁻⁶ is achieved... - 4 The absorbance of a g / mL acetonitrile solution to light at a wavelength of 370 nm is 3 × 10⁻⁶ g / mL. -2 The residual amount of the above-mentioned photopolymerization initiator can be less than 200 ppm. According to the research of the inventors, if a large amount of photopolymerization initiator with an absorbance of more than a certain value at a wavelength of 370 nm remains, fine foaming may sometimes occur when using the adhesive sheet. For foaming, the absorption of the photopolymerization initiator caused by visible light in the near-ultraviolet region may have an effect. Suppressing the residual amount of this photopolymerization initiator in the formed adhesive sheet can help suppress the above-mentioned foaming.
[0128] The residual amount of the aforementioned photopolymerization initiator, which is a characteristic of the adhesive composition, can be evaluated specifically by the steps described in the examples (including the step of forming an adhesive sheet from the adhesive composition).
[0129] The content of photopolymerization initiator in the photocurable adhesive composition (A) is, for example, 0.02 to 10 parts by weight of monomer component M per 100 parts by weight, and can be 0.05 to 5 parts by weight, 0.1 to 3 parts by weight, or even 0.2 to 2 parts by weight.
[0130] The photocurable adhesive composition (A) may contain a crosslinking agent. Examples of crosslinking agents are polyfunctional monomers having two or more polymerizable functional groups in one molecule. The polyfunctional monomer may be a (meth)acrylic acid monomer. Examples of polyfunctional monomers include monomers having two or more C=C bonds in one molecule, and monomers having one or more C=C bonds and one or more polymerizable functional groups such as epoxy, aziridinyl, α-azolinyl, hydrazyl, and hydroxymethyl in one molecule. Preferably, the polyfunctional monomer is a monomer having two or more C=C bonds in one molecule.
[0131] Examples of multifunctional monomers include: polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (NDDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, and other multifunctional acrylates (ester compounds formed by polyols and (meth)acrylic acid, etc.); allyl methacrylate, vinyl methacrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The multifunctional monomer is preferably a multifunctional acrylate, more preferably trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, or dipentaerythritol hexa(meth)acrylate.
[0132] The amount of crosslinking agent varies depending on the molecular weight, number of functional groups, etc., and is, for example, 5 parts by weight or less per 100 parts by weight of monomer component M, but can be 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, and further can be 0.5 parts by weight or less. The lower limit of the amount is, for example, 0.01 parts by weight or more, and further can be 0.05 parts by weight or more.
[0133] The light-curing adhesive composition (A) may contain additives other than those described above. Examples of additives include chain transfer agents, silane coupling agents, viscosity modifiers, tackifiers, plasticizers, softeners, anti-aging agents, fillers, colorants, antioxidants, surfactants, antistatic agents, and ultraviolet absorbers.
[0134] The amount of silane coupling agent relative to 100 parts by weight of monomer component M is, for example, 3 parts by weight or less, and can be 2 parts by weight or less, 1 part by weight or less, or even 0.5 parts by weight or less. The lower limit of the amount is, for example, 0.1 parts by weight or more, and even 0.2 parts by weight or more. The adhesive composition (A) may also not contain silane coupling agent.
[0135] The solvent content in the photocurable adhesive composition (A) is, for example, 5% by weight or less, and can be 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, and further, 0.5% by weight or less. The photocurable adhesive composition (A) may substantially not contain solvent. "Substantially not containing solvent" means that it is permissible to include solvents from additives, etc., at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, and more preferably 0.01% by weight or less.
[0136] The viscosity of the photocurable adhesive composition (A) is preferably 5 to 100 poise at 25°C. The adhesive composition (A) having a viscosity within the above range is particularly suitable for the formation of the coating layer described later.
[0137] <1-4-2. Thermosetting type>
[0138] The adhesive composition (A) may be thermosetting. The components that may be included in the thermosetting adhesive composition (A) are described below.
[0139] Thermosetting adhesive compositions (A) typically contain a base polymer as a monomer component M. The base polymer can be formed by various known polymerization methods such as solution polymerization, radiation polymerization utilizing electron beams, ultraviolet light, etc., bulk polymerization, and emulsion polymerization. Polymerization is typically free radical polymerization. The base polymer can be any copolymer such as random copolymers, block copolymers, graft copolymers, etc. However, the method of forming the base polymer is not limited to the examples described above.
[0140] The weight-average molecular weight of the base polymer is, for example, 700,000 or more, but can be 800,000 or more, 900,000 or more, or even 1 million or more. The upper limit of the weight-average molecular weight is, for example, below 2 million, but can be below 1.8 million, 1.6 million or even below 1.5 million.
[0141] Solution polymerization can be carried out using known polymerization solvents such as ethyl acetate and toluene. Solution polymerization can be conducted, for example, with the use of a polymerization initiator and under a gas stream of inert gas such as nitrogen. Polymerization conditions are, for example, 50–70°C and 5–30 hours.
[0142] There are no particular limitations on the polymerization initiators, chain transfer agents, emulsifiers, etc. used in free radical polymerization, and appropriate choices can be made.
[0143] The thermosetting adhesive composition (A) may include a crosslinking agent. Examples of crosslinking agents are isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, imine crosslinking agents, and multifunctional metal chelates. The thermosetting adhesive composition (A) preferably includes an isocyanate crosslinking agent and / or a peroxide crosslinking agent, and more preferably an isocyanate crosslinking agent.
[0144] As isocyanate crosslinking agents, compounds having at least two isocyanate groups (isocyanate compounds) can be used. The number of isocyanate groups in the isocyanate compound is preferably three or more. There is no particular upper limit to the number of isocyanate groups, for example, five. Examples of isocyanate compounds include aromatic isocyanate compounds, alicyclic isocyanate compounds, and aliphatic isocyanate compounds.
[0145] Examples of aromatic isocyanate compounds include phenyl diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and phenyl dimethyl diisocyanate.
[0146] Examples of alicyclic isocyanate compounds include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated phenyl diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylphenyl diisocyanate.
[0147] Examples of aliphatic isocyanate compounds include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylidene diisocyanate, 1,3-butylidene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0148] Isocyanate crosslinking agents can be polymers (dimers, trimers, pentamers, etc.) of the above-mentioned isocyanate compounds, adducts obtained by addition reactions with polyols such as trimethylolpropane, urea-modified compounds, biuret-modified compounds, urethane-modified compounds, isocyanurate-modified compounds, carbodiimide-modified compounds, and urethane prepolymers obtained by addition reactions with polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, etc.
[0149] Isocyanate crosslinking agents are preferably aromatic isocyanate compounds and their derivatives, more preferably toluene diisocyanate and its derivatives, i.e., toluene diisocyanate (TDI) crosslinking agents. From a reactivity point of view, TDI crosslinking agents are more suitable than phenyl diisocyanate and its derivatives, i.e., phenyl diisocyanate (XDI) crosslinking agents. Isocyanate crosslinking agents may include adducts of polyols and toluene diisocyanate as TDI crosslinking agents. Specific examples of adducts are trimethylolpropane / toluene diisocyanate trimer adducts.
[0150] Commercially available isocyanate crosslinking agents can be used. Examples of commercially available products include Millionate MT, Millionate MTL, Millionate MR-200, Millionate MR-400, CORONATE L, CORONATE HL, CORONATE HX (all manufactured by Tosoh Corporation), TAKENATE D-101E, TAKENATE D-110N, TAKENATE D-120N, TAKENATED-140N, TAKENATE D-160N, TAKENATE D-165N, TAKENATE D-170HN, TAKENATE D-178N, TAKENATE 500, and TAKENATE 600 (all manufactured by Mitsui Chemicals Corporation). Among these, TAKENATE D-101E and TAKENATE D110N are preferred.
[0151] Isocyanate crosslinking agents can be used alone or in combination of two or more.
[0152] The amount of crosslinking agent in the thermosetting adhesive composition (A) is, for example, 0.01 to 20 parts by weight relative to 100 parts by weight of the base polymer.
[0153] The thermosetting adhesive composition (A) may further include known additives. Examples of additives include silane coupling agents, solvents, colorants, pigments, powders, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particles, and foils.
[0154] The thermosetting adhesive composition (A) may also substantially not contain photocuring agents such as photopolymerization initiators.
[0155] 1-5. Other Ingredients
[0156] The adhesive composition (A) may contain other components than those described above.
[0157] <1-5-1. Inorganic Particles>
[0158] The adhesive composition (A) may further contain inorganic particles. The inorganic particles are preferably dispersed in the adhesive composition (A).
[0159] Inorganic particles can be selected from one or more metal compound particles and metal particles, for example, according to desired purposes such as increasing the refractive index. Metal compound particles can be metal oxide particles. Examples of materials constituting metal compound particles are titanium oxide, zirconium oxide, cerium oxide, aluminum oxide, zinc oxide, tin oxide, copper oxide, barium titanate, and niobium oxide. Metal oxide particles can be used alone or in combination of two or more. The inorganic particles preferably include zirconium oxide, and can be zirconium oxide particles that are substantially composed of only zirconium oxide. Zirconia particles can help increase the refractive index of the adhesive sheet.
[0160] Materials constituting metal compound particles can be metal hydroxides such as aluminum hydroxide, boehmite, magnesium hydroxide, calcium hydroxide, zinc hydroxide, iron hydroxide, copper hydroxide, barium hydroxide, basic magnesium carbonate, and hydrotalcite, as well as hydrated metal compounds. Examples of materials constituting metal particles include iron, zinc, tungsten, and platinum.
[0161] Inorganic particle materials can be high-entropy alloys composed of a mixture of multiple elements.
[0162] The inorganic particles can be surface-treated particles. One example of surface treatment is hydrophobication. It should be noted that, in this specification, the inorganic particles preferably do not contain carbon black particles.
[0163] Inorganic particles can contain high-refractive-index materials. The refractive index of a high-refractive-index material is, for example, 1.60 or higher, and can be 1.70 or higher, 1.80 or higher, or even 2.00 or higher. There is no particular upper limit to the refractive index of high-refractive-index materials; for example, it can be below 3.00, below 2.80, below 2.50, or even below 2.20. The refractive index of the material contained in the inorganic particles can be determined by measuring the refractive index of a single-layer film of the material using a commercially available spectroellipsometer at 23°C and 549 nm. For example, a spectroellipsometer with the product name "EC-400" (manufactured by JA. Woolam) or an equivalent can be used.
[0164] Inorganic particles can be nanoparticles with an average particle size of less than 1 μm. The average particle size of inorganic particles can be less than 100 nm. The average particle size can be less than 70 nm, less than 50 nm, less than 30 nm, less than 20 nm, less than 15 nm, less than 10 nm, less than 7 nm, less than 5 nm, and further less than 4 nm. The lower limit of the average particle size is, for example, greater than 1 nm, greater than 1.5 nm, greater than 2 nm, and further greater than 2.5 nm. It should be noted that the average particle size can be determined as the median particle size (D50) in the particle size distribution measured by dynamic light scattering method.
[0165] The content of inorganic particles (specifically, a mixture of inorganic particles and a dispersant) in the adhesive composition (A) is, for example, 1 part by weight or more relative to 100 parts by weight of monomer component M and its polymer, and can be 3 parts by weight or more, 5 parts by weight or more, 10 parts by weight or more, 20 parts by weight or more, 35 parts by weight or more, 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 90 parts by weight or more, and further can be 95 parts by weight or more. The upper limit of the content relative to 100 parts by weight of monomer component M and its polymer is, for example, 200 parts by weight or less, and can be 170 parts by weight or less, 150 parts by weight or less, 130 parts by weight or less, 120 parts by weight or less, 110 parts by weight or less, and further can be 100 parts by weight or less. It should be noted that the content of inorganic particles in the adhesive composition (A) generally corresponds approximately to the content of inorganic particles in the adhesive sheet formed from the adhesive composition (A). Therefore, the content of inorganic particles in the adhesive composition (A) can be understood as the content of inorganic particles in the adhesive sheet.
[0166] <1-5-2. Dispersants>
[0167] The adhesive composition (A) may further include a dispersant for the inorganic particles. The dispersant is a component used to adequately disperse the inorganic particles in the adhesive composition. Preferably, the dispersant is in contact with the surface of the inorganic particles, and more preferably coats the surface of the inorganic particles.
[0168] Examples of dispersants are compounds that have both hydrophilic and hydrophobic portions within a single molecule. It is presumed that the hydrophilic and hydrophobic portions of the dispersant exhibit relatively high affinity for inorganic particles, as well as for the monomeric component M and its polymers. Dispersants may or may not possess polymerizable functional groups such as olefinic unsaturated groups.
[0169] The hydrophilic portion of the dispersant preferably has a hydrophilic group. Examples of hydrophilic groups include ether groups and ester groups.
[0170] The hydrophilic portion of the dispersant preferably has a functional group F that exhibits adsorption or reactivity to inorganic particles. Examples of functional group F are at least one selected from basic and acidic groups. Specific examples of functional group F are hydroxyl, carboxyl, nitrogen-containing, sulfur-containing, phosphorus-containing, and silicon-containing groups. The number of functional groups F in one molecule of the dispersant can be one or more (e.g., about 2 to 5). The two or more functional groups F present in one molecule can be of the same type or different types.
[0171] The hydrophilic portion of the dispersant can have a chain-like structure or a composite structure of chain-like and ring-like structures. For example, the dispersant may include: a structure in which a functional group F is linked to a hydrophobic portion via a chain-like structure; a structure in which the side chains of the chain-like structure connected to the hydrophobic portion at one end have the functional group F; and a structure in which the other end of the chain-like structure connected to the hydrophobic portion does not have the functional group F (e.g., the other end of the chain-like structure is a free end). The dispersant may have two or more of the above structures.
[0172] The dispersant can be an aliphatic compound. An aliphatic compound is represented, for example, by the following formula (1).
[0173] [Chemical Formula 1]
[0174] In formula (1), R is an alkyl group, preferably an alkyl group with 1 to 3 carbon atoms, more preferably an ethyl group. m is 1 to 10, preferably 2 to 8, more preferably 3 to 7. n is 5 to 20, preferably 8 to 12.
[0175] The dispersant can be an aromatic compound having an aromatic ring. Examples of aromatic rings are the same as those described above in the description of monomer a.
[0176] The dispersant can be selected from known surfactants. Examples of surfactants include anionic surfactants (carboxylic acid type, phosphate ester type, sulfate ester type, sulfonic acid type, etc.), nonionic surfactants, cationic surfactants, and amphoteric surfactants. Anionic surfactants are preferred as dispersants.
[0177] The content of dispersant relative to 100 parts by weight of inorganic particles is, for example, 0.1 parts by weight or more, 0.5 parts by weight or more, and further, 1.0 parts by weight or more. The upper limit of the content is, for example, 30 parts by weight or less, and 20 parts by weight or less. Similar to the content of inorganic particles, the content of dispersant in the adhesive composition (A) can be understood as the content of dispersant in the adhesive sheet.
[0178] <1-5-3. Polymer B>
[0179] The adhesive composition (A) may further comprise polymer B with a weight-average molecular weight of 1,500 to 30,000. Polymer B, depending on its composition, can function as a tackifier.
[0180] The weight-average molecular weight of polymer B can be below 25,000, or below 20,000, 18,000, 16,000, 15,000, 13,000, 10,000, 8,000, and further below 6,000. The lower limit of the weight-average molecular weight is above 1,500, and can be above 2,000, or above 2,500, 3,000, 3,500, and further above 4,000. The weight-average molecular weight can be between 2,000 and 16,000, preferably between 4,000 and 16,000. The weight-average molecular weight is determined by measuring it using GPC (gel permeation chromatography) and calculating it using polystyrene conversion.
[0181] Polymer B preferably comprises a building block derived from monomer b having a double-bonded ring. Polymer B comprising building blocks derived from monomer b can contribute to increasing the refractive index of the adhesive sheet. Monomer b can be the monomer described above for monomer a. Monomer b may be the same as or different from monomer a.
[0182] In monomer b, the double-bonded ring is preferably an aromatic ring. Monomer b may contain two or more aromatic rings (preferably carbocyclic rings) in one molecule, and is more preferably a monomer (containing multiple aromatic ring monomers) having two or more aromatic rings and at least one olefinic unsaturated group in one molecule. Monomer b particularly preferably contains phenoxybenzyl acrylate.
[0183] The content of constituent units derived from monomer b in polymer B is, for example, 10% by weight or more, and can be 30% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 97% by weight or more, 98% by weight or more, 99% by weight or more, and further, 100% by weight. The above content may, depending on the circumstances, be less than 10% by weight, less than 5% by weight, and further, less than 1% by weight. Polymer B may also not contain constituent units derived from monomer b.
[0184] Polymer B may contain constituent units derived from monomers other than monomer b described above. Examples of other monomers include the monomers described above for monomer component M (hydroxyl-containing monomers, alkyl (meth)acrylates with alkyl groups having 1 to 20 carbon atoms in the side chain, aliphatic ring monomers, and carboxyl-containing monomers).
[0185] The content of constituent units derived from hydroxyl-containing monomers in polymer B is, for example, 25% by weight or less, and can be 20% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, and further, 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, and further, 0.5% by weight or more. Polymer B may also not contain constituent units derived from hydroxyl-containing monomers.
[0186] The content of (meth)acrylate-derived constituent units in polymer B is, for example, 50% by weight or less, and can be 40% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, 7% by weight or less, 5% by weight or less, and further, 4% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. The lower limit of the content may be 50% by weight or more, depending on the circumstances. Polymer B may also not contain constituent units derived from (meth)acrylate.
[0187] The content of constituent units derived from aliphatic ring monomers in polymer B is, for example, 50% by weight or less, but can be 40% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, 7% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, and further, 2% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, but can be 0.1% by weight or more, 0.5% by weight or more, and further, 1% by weight or more. The lower limit of the content may, depending on the circumstances, be 50% by weight or more, 80% by weight or more, and further, 90% by weight or more. Polymer B may also not contain constituent units derived from aliphatic ring monomers.
[0188] The content of carboxyl-containing monomer-derived constituent units in polymer B is, for example, 10% by weight or less, and can be 7% by weight or less, 5% by weight or less, 3% by weight or less, or even 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, 0.5% by weight or more, or even 1% by weight or more. Polymer B preferably does not contain constituent units derived from carboxyl-containing monomers.
[0189] Another example of other monomers is a nitrogen-containing monomer. A nitrogen-containing monomer is a monomer that has at least one nitrogen atom within a molecule (within one molecule).
[0190] Examples of nitrogen-containing monomers include N-vinylcyclic amides and (meth)acrylamide. It should be noted that nitrogen-containing monomers can be used alone or in combination of two or more.
[0191] Examples of N-vinylcyclic amides include N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidinone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3-azin-2-one, N-vinyl-3,5-morpholinedione, and vinylmethylazolidinone. Examples of (meth)acrylamides include (meth)acrylamide, N-alkyl (meth)acrylamide, and N,N-dialkyl (meth)acrylamide. (Methacrylamides) also include various N-hydroxyalkyl (meth)acrylamides and N-alkoxyalkyl (meth)acrylamides.
[0192] Examples of nitrogen-containing monomers other than N-vinylcyclic amides and (meth)acrylamide include amino ethyl methacrylate, dimethylaminoethyl methacrylate, dimethylaminopropyl methacrylate, and tert-butylaminoethyl methacrylate; cyano monomers such as acrylonitrile and methacrylonitrile; and monomers containing amino groups such as (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazolium, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinylpyrazole, vinylisopyrazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, and N-methylvinylpyridine. Monomers containing heterocyclic groups, such as pyrrolidone; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitconimide, N-ethylitconimide, N-butylitconimide, N-octylitconimide, N-2-ethylhexylitconimide, N-laurylitconimide, and N-cyclohexylitconimide; succinimide monomers containing imide groups, such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxohexamethylenesuccinimide, and N-(meth)acryloyl-8-oxooctamethylenesuccinimide; and isocyanate-containing monomers, such as 2-(meth)acryloyloxyethyl isocyanate.
[0193] The content of nitrogen-containing monomers in polymer B is, for example, 25% by weight or less, and can be 20% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, and further, 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, and further, 0.5% by weight or more. Polymer B may also not contain any nitrogen-containing monomers.
[0194] Another example of other monomers is an ether-containing monomer. An ether-containing monomer has at least one ether group and at least one olefinically unsaturated group in one molecule. It should be noted that ether-containing monomers can be used alone or in combination of two or more.
[0195] Examples of olefinic unsaturated groups are the same as those described above in the description of monomer a. Ether-containing monomers may be (meth)acrylic acid monomers.
[0196] Examples of ether-containing monomers are 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxydipropylene glycol (meth)acrylate. The preferred ether-containing monomer is 2-(2-ethoxyethoxy)ethyl acrylate (CBA).
[0197] The content of constituent units derived from ether-containing monomers in polymer B is, for example, 25% by weight or less, and can be 20% by weight or less, 15% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, and further, 1% by weight or less. The lower limit of the content is, for example, 0.01% by weight or more, and can be 0.1% by weight or more, and further, 0.5% by weight or more. Polymer B may also not contain constituent units derived from ether-containing monomers.
[0198] Polymer B can be produced using known polymerization methods such as solution polymerization, radiation polymerization, bulk polymerization, emulsion polymerization, and polymerization under supercritical conditions, including free radical polymerization. Examples of radiation that can be used in radiation polymerization include electron beams, UV radiation, and microwaves. The resulting polymer B can be any copolymer, such as random copolymers, block copolymers, or graft copolymers.
[0199] When the adhesive composition (A) contains polymer B, the content of polymer B relative to 100 parts by weight of monomer component M is, for example, 0.1 parts by weight or more, and can be 0.5 parts by weight or more, 1.0 parts by weight or more, 2.0 parts by weight or more, 3.0 parts by weight or more, 4.0 parts by weight or more, 5.0 parts by weight or more, 6.0 parts by weight or more, 7.0 parts by weight or more, 8.0 parts by weight or more, 9.0 parts by weight or more, 10.0 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, and further, 40 parts by weight or more. The upper limit of the above content is, for example, 60 parts by weight or less, and can be 55 parts by weight or less, 50 parts by weight or less, and further, 45 parts by weight or less.
[0200] When the adhesive composition (A) comprises inorganic particles and polymer B, the content of polymer B, relative to the monomer component M, its polymer, and inorganic particles (specifically, a mixture of inorganic particles and dispersant) totaling 100 parts by weight, is, for example, 0.1 parts by weight or more, and can be 0.5 parts by weight or more, 1 part by weight or more, 2 parts by weight or more, 3 parts by weight or more, 4 parts by weight or more, 5 parts by weight or more, 6 parts by weight or more, 7 parts by weight or more, 8 parts by weight or more, 9 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, and further, 20 parts by weight or more. The upper limit of the above content is, for example, 50 parts by weight or less, and can be 40 parts by weight or less, 35 parts by weight or less, and further, 30 parts by weight or less. The above content is preferably 1 to 30 parts by weight, and more preferably 2 to 30 parts by weight.
[0201] 1-6. Other Implementation Methods
[0202] In other embodiments of the present invention, the adhesive composition (a) comprises at least one monomeric component M containing phenoxybenzyl acrylate and its polymers, and UVA. The adhesive composition (a) may contain any combination of the above-described components as possible components in the adhesive composition (A). The adhesive composition (a) may be photocurable or thermocurable. The adhesive composition (a) may have any combination of the above-described properties as possible properties of the adhesive composition (A). An adhesive sheet according to an embodiment of the present invention can be formed from the adhesive composition (a). The adhesive sheet formed from the adhesive composition (a) may have a refractive index of 1.55 or higher.
[0203] 2. Adhesive Sheet
[0204] 2-1. Adhesive Sheet
[0205] An example of an adhesive sheet according to an embodiment of the present invention is shown below. Figure 1 . Figure 1The adhesive sheet 1 is an adhesive sheet formed from an adhesive composition (A).
[0206] The refractive index n2 of the adhesive sheet 1 can be 1.55 or higher. The refractive index n2 can be 1.56 or higher, 1.57 or higher, 1.58 or higher, 1.59 or higher, 1.60 or higher, 1.61 or higher, 1.62 or higher, 1.63 or higher, and further, 1.64 or higher. The upper limit of the refractive index n2 is, for example, 1.70 or lower, and can be 1.69 or lower, 1.68 or lower, 1.67 or lower, 1.66 or lower, 1.65 or lower, 1.64 or lower, 1.63 or lower, and further, 1.62 or lower. The optical substrates that can be included in the optical laminate include high-refractive-index optical substrates. Using a high-refractive-index adhesive sheet 1 in the bonding of this optical substrate is beneficial for reducing reflected light at the interface between the optical substrate and the adhesive sheet.
[0207] The haze of adhesive sheet 1 can be 2.0% or less. The haze can be 1.7% or less, 1.5% or less, 1.2% or less, 1.0% or less, 0.9% or less, 0.8% or less, and further, 0.7% or less. There is no particular limitation on the lower limit of haze, and it can be 0.1% or more.
[0208] Regarding the transmittance in the thickness direction of the adhesive sheet 1, it can be 25% or less for light with a wavelength of 380 nm and more than 80% for light with a wavelength of 420 nm. The transmittance for light with a wavelength of 380 nm can be less than 20%, 18%, 16%, 15%, 13%, 11%, 10%, 9%, 7%, 5%, 4%, 2%, and further less than 1%. The lower limit of this transmittance is 0%. The transmittance for light with a wavelength of 420 nm can be more than 82%, 84%, 85%, 87%, 88%, and further more than 90%. The upper limit of this transmittance is not particularly limited and can be less than 95%. The adhesive sheet 1, with its suppressed transmittance for light with a wavelength of 380 nm, is particularly suitable for improving durability against ultraviolet light.
[0209] The colorimetric properties of the adhesive sheet conform to CIE 1976 L as specified in JIS Z8781-4:2013. ,a ,b Color saturation in a color space The absolute value can be below 2.0. (Chromaticity) The absolute value can be below 1.7, below 1.5, below 1.2, below 1.0, below 0.9, below 0.8, and even below 0.7. (Colorimetry) The lower limit of the absolute value is 0, and it can be greater than 0.1.
[0210] The adhesive sheet 1 can have two or more properties selected from the above-mentioned haze, light transmittance and colorimetry in any combination.
[0211] Adhesive sheet 1 can be included in a formulation with a concentration of 1×10 -4 The absorbance of a g / mL acetonitrile solution to light at a wavelength of 370 nm is 3 × 10⁻⁶ g / mL. -2 The above are photopolymerization initiators.
[0212] The residual amount of photopolymerization initiator in adhesive sheet 1 can be less than 200 ppm. Furthermore, in adhesive sheet 1, when a concentration of 1×10⁻⁶ is achieved... -4 The absorbance of a g / mL acetonitrile solution to light at a wavelength of 370 nm is 3 × 10⁻⁶ g / mL. -2 The residual amount of the above photopolymerization initiator can be below 200 ppm.
[0213] The gel fraction of adhesive sheet 1 is, for example, 50% or more, 75% or more, 80% or more, or even 85% or more.
[0214] The thickness of the adhesive sheet 1 is, for example, 2~500μm, and can be 2~300μm, 2~200μm, or even 2~150μm. The upper limit of the thickness can be less than 100μm, and can be less than 70μm, less than 60μm, less than 55μm, less than 50μm, less than 45μm, less than 40μm, less than 35μm, or even less than 30μm. The lower limit of the thickness can be more than 5μm, more than 10μm, more than 15μm, more than 20μm, more than 25μm, more than 30μm, more than 35μm, more than 40μm, more than 45μm, or even more than 50μm.
[0215] The adhesive sheet 1 can be used, for example, in optical laminates and image display devices. However, the uses of the adhesive sheet 1 are not limited to the examples described above.
[0216] 2-2. Manufacturing Method
[0217] The adhesive sheet 1 formed from the photocurable adhesive composition (A) can be formed, for example, by irradiating a first laminate 10, which sequentially comprises a substrate sheet 11, a coating layer 12 containing the adhesive composition (A), and a release liner 13, with light 14 (see reference). Figure 2 The coating layer 12 is cured by irradiation with light 14, forming the adhesive sheet 1. Typically, the irradiation with light 14 is performed from one side of the substrate sheet 11. In this case, the light 14 passes through the substrate sheet 11 and reaches the coating layer 12, causing the coating layer 12 to cure. However, it should be noted that the irradiation with light 14 can also be performed from one side of the release liner 13, or from both sides of the release liner 13 and the substrate sheet 11.
[0218] The formed adhesive sheet 1 is sandwiched between the substrate sheet 11 and the release liner 13 until the release liner 13 is peeled off, thus forming part of the second laminate 17. By peeling the release liner 13 from the second laminate 17, a third laminate 15 comprising the substrate sheet 11 and the adhesive sheet 1 is obtained. In the third laminate 15, the surface of the adhesive sheet 1 is exposed. Optical films can be laminated directly or via other layers relative to the exposed surface of the adhesive sheet 1.
[0219] Light 14 is, for example, visible light or ultraviolet light with a wavelength shorter than 450 nm. The light may contain wavelengths in the same region as the absorption wavelength of the photopolymerization initiator contained in the adhesive composition (A). Light obtained by blocking short-wavelength light (below 300 nm) through a filter or similar means can be irradiated; blocking the short-wavelength light is suitable for suppressing the deterioration of the substrate sheet 11 and / or release liner 13 caused by light 14. The light source 18 is, for example, a lighting device equipped with an ultraviolet irradiation lamp. Examples of ultraviolet irradiation lamps include ultraviolet LEDs, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, microwave-excited mercury lamps, black lights, chemical lamps, germicidal lamps, low-pressure discharge mercury lamps, and excimer lasers. Two or more ultraviolet irradiation lamps may also be combined.
[0220] The illuminance of light 14 irradiating the first layer stack 10 (specifically, the coating layer 12) is, for example, 2.0~30 mW / cm². 2 The illuminance can be 2.5 mW / cm². 2 Above, 3.0mW / cm 2 Above, 3.5mW / cm 2 Above, 4.0mW / cm 2 Above, 5.0mW / cm 2 Above, 6.0mW / cm 2 Above, 7.0mW / cm 2 Above, 8.0mW / cm 2 Above, 9.0mW / cm 2 The above, and thus can be 10mW / cm 2 The above. The upper limit for illuminance is, for example, 25 mW / cm². 2 The following can be 20mW / cm 2 the following.
[0221] The duration of illumination 14 on the first layer stack 10 (specifically, the coating layer 12) is, for example, from 10 seconds to 1000 seconds, and can be 60 seconds or more, 100 seconds or more, 150 seconds or more, and further, 200 seconds or more. The upper limit of the duration is, for example, 800 seconds or less, and can be 600 seconds or less, 500 seconds or less, 400 seconds or less, 300 seconds or less, and further, 250 seconds or less. The illumination 14 can be continuous or intermittent.
[0222] The cumulative light intensity of light 14 for the first layer stack 10 (specifically, coating layer 12) is, for example, 25 mJ / cm. 2 The above can be 100mJ / cm 2 Above 500mJ / cm 2 Above, 1000mJ / cm 2 Above, 2000mJ / cm 2 Above, 2500mJ / cm 2 Above, 3000mJ / cm 2 Above 5000mJ / cm 2 Above, 7500mJ / cm 2 The above, and thus can be 10000 mJ / cm 2 That's all. There is no specific upper limit for the cumulative light intensity, for example, 30000 mJ / cm². 2 The following can be 25000mJ / cm 2 Below, 20000mJ / cm 2 The following, and further, can be 18000mJ / cm 2 the following.
[0223] Light 14 can irradiate the first layer stack 10 in multiple stages. The illuminance and / or cumulative light intensity of light 14 in each stage can be the same or different. In addition, the light sources in each stage can be the same or different.
[0224] An example of the substrate for peeling liner 13 (hereinafter referred to as "liner substrate") is a resin film. Examples of resins that may be included in the liner substrate include polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth)acrylic resin, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.
[0225] The release liner 13 may also have layers other than the substrate. The release liner 13 may have a release layer. For example, the release liner 13 may have a substrate and a release layer formed on one side of the substrate. The release liner 13 can be used such that the release layer is on the side of the coating layer 12. Typically, the release layer is a cured layer of a release agent composition containing a release agent. Various release agents can be used, such as silicone-based release agents, fluorinated release agents, long-chain alkyl release agents, fatty acid amide release agents, and silica powder.
[0226] The peeling liner 13 can be in the form of a single sheet or in the form of a strip.
[0227] An example of substrate sheet 11 is a resin film. Examples of resins contained in substrate sheet 11 are the same as examples of resins that may be contained in a liner substrate.
[0228] The thickness of the substrate sheet 11 is, for example, 10~200μm, or 25~150μm.
[0229] The substrate sheet 11 may have a release layer on one side of the coating layer 12. Examples of release layers that the substrate sheet 11 may have are the same as examples of release layers that the release liner 13 may have. Alternatively, release layers may be present on both the release liner 13 and the substrate sheet 11.
[0230] The substrate sheet 11 can typically be selected as a sheet with a greater peel force to the adhesive sheet 1 compared to the release liner 13.
[0231] The substrate sheet 11 can be a single sheet or a strip.
[0232] The first laminate 10 can be formed, for example, by forming a coating layer 12 on a substrate sheet 11 (or release liner 13) and placing a release liner 13 (or substrate sheet 11) on the formed coating layer 12. Alternatively, the first laminate 10 can be formed by coating in such a way that a photocurable composition flows into a space between a substrate sheet 11 and a release liner 13 held at a given interval with their main surfaces facing each other.
[0233] The coating layer 12 can be formed by various coating methods such as roller coating, roller licking coating, gravure coating, reverse coating, roller brushing, spraying, dip roller coating, bar coating, scraping coating, air knife coating, curtain coating, die lip coating, and die coating.
[0234] The thickness of the coating layer 12 can be adjusted according to the thickness of the target adhesive sheet 1, for example, from 2 to 500 μm, or from 2 to 300 μm, 2 to 200 μm, or even from 2 to 150 μm. The upper limit of the thickness can be less than 100 μm, or less than 70 μm, 60 μm, 50 μm, 40 μm, 30 μm, 25 μm, or even less than 20 μm. The lower limit of the thickness can be greater than 5 μm, greater than 10 μm, or even greater than 15 μm.
[0235] The first laminate 10 may include a strip-shaped substrate sheet 11, a strip-shaped coating layer 12, and a strip-shaped release liner 13; in other words, it may be strip-shaped. The strip-shaped first laminate 10 can be obtained, for example, by forming the coating layer 12 between the substrate sheet 11 and the release liner 13 while they are being continuously fed from the winding body.
[0236] An adhesive sheet 1 formed from a thermosetting adhesive composition (A) can be formed, for example, by drying a coating film of the adhesive composition (A) disposed on a substrate sheet. Drying can be performed using heat. A release film can be used as the substrate sheet. The adhesive sheet 1 formed on the release film can be transferred to other layers that may be included in the optical laminate 1. A known film can be used as the release film. The substrate sheet can be other layers that may be included in the optical laminate.
[0237] The drying temperature of the coated film is, for example, below 130°C, and can be below 125°C, below 120°C, below 110°C, or even below 100°C. The drying temperature is, for example, above 60°C, and can be above 80°C. The drying time of the coated film can be appropriately adjusted according to the composition of the adhesive composition (A), for example, from 30 seconds to 300 seconds, from 40 seconds to 240 seconds, or even from 60 seconds to 180 seconds.
[0238] 3. Optical Laminates
[0239] An example of an optical laminate according to an embodiment of the present invention is shown below. Figure 3 . Figure 3 The optical laminate 20A includes an adhesive sheet 1 and an optical film 2. The adhesive sheet 1 and the optical film 2 are laminated together. The optical laminate 20A can be used in the form of an optical film with an adhesive sheet.
[0240] Examples of optical film 2 are polarizing films, retardation films, and laminated films comprising polarizing films and / or retardation films. However, optical film 2 is not limited to the examples described above. Optical film 2 may also comprise a glass film.
[0241] Optical film 2 is a polarizing film, and adhesive sheet 1 can be attached to optical film 2.
[0242] A polarizing film includes a polarizer. Typically, a polarizing film includes a polarizer and a protective film (a transparent protective film). The protective film is disposed in contact with the ground, for example, the main surface (the surface with the widest area) of the polarizer. The polarizer may be disposed between two protective films. The protective film may be disposed on at least one side of the polarizer.
[0243] There are no particular limitations on what constitutes a polarizer. Examples include: polarizers obtained by uniaxially stretching hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified ethylene-vinyl acetate copolymer films, after adsorbing dichroic substances such as iodine and dichroic dyes onto them; and polyene-oriented films such as dehydrated polyvinyl alcohol products and dehydrochlorinated polyvinyl chloride products. Typically, a polarizer is formed from a polyvinyl alcohol film (which may contain partially saponified ethylene-vinyl acetate copolymer films) and dichroic substances such as iodine.
[0244] The thickness of the polarizer is not particularly limited; for example, it can be 80 μm or less, but can be 50 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 18 μm or less, 15 μm or less, and even 12 μm or less. The lower limit of the polarizer's thickness is not particularly limited; for example, it can be 1 μm or more, but can be 5 μm or more, and even 10 μm or more. The lower limit of the polarizer's thickness can be 15 μm or more, depending on the situation. Suppressing dimensional variations in thin polarizers (e.g., thickness 20 μm or less) contributes to improving the durability of optical laminates, especially their durability at high temperatures.
[0245] The polarizer preferably exhibits absorption dichroism at any wavelength within the range of 380 nm to 780 nm. The single-unit transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 42.0% to 46.0%, more preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or higher, more preferably 99.0% or higher, and even more preferably 99.9% or higher.
[0246] Polarizers can be manufactured using any suitable method. Specifically, polarizers can be made from a single layer of resin film or from a laminate of two or more layers.
[0247] A method for fabricating a polarizing mirror from the aforementioned single-layer resin film typically includes: dyeing the resin film using dichroic substances such as iodine or dichroic dyes, and performing a stretching treatment. For example, hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films can be used. The method may further include insolubility treatment, swelling treatment, crosslinking treatment, etc. Such manufacturing methods are well-known and commonly used in the art, therefore detailed descriptions are omitted.
[0248] The polarizing mirror obtained using the above-described laminate can be manufactured, for example, using a laminate of a resin substrate and a resin film or resin layer (typically a PVA-based resin layer). Specifically, it can be manufactured by: coating a PVA-based resin solution onto a resin substrate, allowing it to dry to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to form a polarizing mirror from the PVA-based resin layer. In this embodiment, it is preferable to form a PVA-based resin layer comprising a halide and a PVA-based resin on one side of the resin substrate. Stretching typically includes immersing the laminate in an aqueous boric acid solution for stretching. Furthermore, stretching may, if necessary, further include stretching the laminate in a gas atmosphere at a high temperature (e.g., above 95°C) before stretching in the aqueous boric acid solution. In addition, in this embodiment, it is preferable to subject the laminate to a drying shrinkage treatment, causing it to shrink by more than 2% in the width direction by heating while being transported along the length direction. Typically, the manufacturing method of this embodiment includes sequentially subjecting the laminate to assisted stretching in a gas atmosphere, dyeing, stretching in an aqueous solution, and drying shrinkage. By introducing assisted stretching, even when PVA is coated on a thermoplastic resin, the crystallinity of PVA can be improved, achieving high optical properties. Furthermore, by simultaneously improving the orientation of PVA beforehand, problems such as reduced orientation and dissolution of PVA during subsequent dyeing and stretching processes and immersion in water can be prevented, achieving high optical properties. Moreover, when the PVA-type resin layer is immersed in a liquid, compared to cases where the PVA-type resin layer does not contain halides, orientation disorder of PVA molecules and reduction of orientation can be suppressed, achieving high optical properties. Furthermore, by using the drying shrinkage treatment to shrink the laminate in the width direction, high optical properties can be achieved. A polarizing film can be obtained by laminating a protective film onto the peeled surface of the resin substrate / polarizer laminate after peeling off the resin substrate, or onto the side opposite to the peeled surface. Detailed descriptions of the manufacturing method of such a polarizer are available in, for example, Japanese Patent Application Publication No. 2012-73580 and Japanese Patent No. 6470455. These publications, in their entirety, are incorporated herein by reference.
[0249] As materials for the protective film, thermoplastic resins with excellent properties such as transparency, mechanical strength, thermal stability, moisture barrier properties, and isotropy can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The protective film material can be thermosetting resins or UV-curable resins such as (meth)acrylic acid, urethane, acrylate urethane, epoxy, and silicone. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different. For example, a protective film formed of thermoplastic resin can be bonded to one main surface of the polarizer via an adhesive, and a protective film formed of thermosetting resin or UV-curable resin can be bonded to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of additives include: ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0250] The thickness of the protective film can be appropriately determined. Generally speaking, it is about 10~200μm, considering factors such as strength, processability, operability, and thinness.
[0251] Polarizing lenses and protective films are typically bonded together using water-based adhesives. Examples of water-based adhesives include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latexes, waterborne polyurethane, and waterborne polyester. Other adhesives besides those mentioned above include UV-curable adhesives and electron beam-curable adhesives. Electron beam-curable polarizing film adhesives exhibit suitable adhesion to various protective films. The adhesive may also contain metallic compound fillers.
[0252] In polarizing films, a phase retardation film or similar material can be formed on the polarizer to replace the protective film. Alternatively, another protective film or a phase retardation film can be applied to the protective film.
[0253] Regarding the protective film, a hard coating can also be applied to the surface opposite to the surface to which the polarizer is bonded, and it can also be treated for purposes such as anti-reflection, anti-adhesion, diffusion, and anti-glare.
[0254] The polarizing film can be a circularly polarizing film.
[0255] The thickness of the polarizing film is, for example, less than 500 μm, less than 300 μm, less than 200 μm, less than 100 μm, and further less than 60 μm. The lower limit of the thickness is, for example, more than 10 μm, more than 25 μm, and further more than 40 μm.
[0256] A retardation film is a film that exhibits birefringence in the in-plane direction and / or the thickness direction. Examples of retardation films include stretched resin films and films obtained by aligning and immobilizing liquid crystal materials.
[0257] The retardation film can be a λ / 4 waveplate, a λ / 2 waveplate, a retardation film for antireflection (see, for example, paragraphs 0221, 0222, and 0228 of Japanese Patent Application Publication No. 2012-133303), a retardation film for viewing angle compensation (see, for example, paragraphs 0225 and 0226 of Japanese Patent Application Publication No. 2012-133303), or a tilted-orientation retardation film for viewing angle compensation (see, for example, paragraph 0227 of Japanese Patent Application Publication No. 2012-13303). The retardation film is not limited to the examples mentioned above as long as it has birefringence in the in-plane direction and / or the thickness direction. There are no limitations on the phase difference value, arrangement angle, three-dimensional birefringence, or whether it is a single layer or multiple layers. Known films can be used for the retardation film.
[0258] The thickness of the optical film 2 is, for example, 1~200 μm.
[0259] The optical film 2 can be a single layer or a laminated film consisting of two or more layers. When the optical film 2 is a laminated film, the bonding of the layers can be achieved using an adhesive sheet 1.
[0260] Another example of an optical laminate according to an embodiment of the present invention is shown below. Figure 4 . Figure 4 The optical laminate 20B has a laminated structure in which a release liner 3, an adhesive sheet 1, and an optical film 2 are sequentially stacked. The optical laminate 20B can be used as an optical film with an adhesive sheet by peeling off the release liner 3.
[0261] The release liner 3 is typically a resin film. Examples of resins constituting the release liner 3 include polyesters such as polyethylene terephthalate (PET), polyolefins such as polyethylene and polypropylene, polycarbonate, acrylics, polystyrene, polyamide, and polyimide. The side of the release liner 3 that is in contact with the adhesive sheet 1 may also be subjected to a release treatment. The release treatment may be, for example, a treatment using an organosilicon compound. However, the release liner 3 is not limited to the examples described above. The release liner 3 can be released when using the optical laminate 20B, for example, when it is adhered to the image forming layer.
[0262] Another example of an optical laminate according to an embodiment of the present invention is shown below. Figure 5 . Figure 5The optical laminate 20C has a laminated structure in which a release liner 3, an adhesive sheet 4, a retardation film 2B, an adhesive sheet 1, and a polarizing film 2A are sequentially stacked. The optical laminate 20C can be used by peeling off the release liner 3 and then attaching it to, for example, an image forming layer.
[0263] Adhesive sheet 4 can be a known adhesive sheet. Adhesive sheet 1 can be used for adhesive sheet 4.
[0264] Another example of an optical laminate according to an embodiment of the present invention is shown below. Figure 6 . Figure 6 The optical laminate 20D has a stacked structure in which a release liner 3, an adhesive sheet 4, a retardation film 2B, an adhesive sheet 1, a polarizing film 2A, and a protective film 5 are sequentially stacked. The optical laminate 20D can be used by peeling off the release liner 3 and then attaching it to, for example, an image forming layer.
[0265] The protective film 5 protects the outermost optical film 2 (polarizer 2A) during the handling and storage of the optical laminate 20D, and also when the optical laminate 20D is introduced into the image display device. Furthermore, when introduced into the image display device, the protective film 5 can function as a window to the external space. The protective film 5 is typically a resin film. The resin constituting the protective film 5 is, for example, polyester such as PET, polyolefins such as polyethylene and polypropylene, acrylics, cycloolefins, polyimide, and polyamide, preferably polyester. However, the protective film 5 is not limited to the above examples. The protective film 5 can be a glass film or a laminate containing a glass film. Surface treatments such as anti-glare, anti-reflection, and antistatic treatments can be applied to the protective film 5.
[0266] The protective film 5 can be bonded to the optical film 2 using any adhesive. It can also be bonded using the adhesive sheet 1.
[0267] Another example of an optical laminate according to an embodiment of the present invention is shown below. Figure 7 . Figure 7 The optical laminate 20E has a laminated structure in which a polarizing film 2A, a first adhesive layer 30, a first retardation film 2B, a second adhesive layer 35, a second retardation film 2C, an adhesive sheet 1, and a release liner 3 are sequentially stacked. The optical laminate 20E can be used by peeling off the release liner 3 and then attaching it to, for example, an image forming layer.
[0268] In the optical laminate 20E, the polarizing film 2A has a laminated structure in which a first protective film 26A, a polarizing mirror 25 and a second protective film 26B are stacked in sequence.
[0269] The first protective film 26A can be formed, for example, from any suitable resin film that can be used as a protective layer for the polarizer 25. Specific examples of resins that are the main components of this resin film include cellulose resins such as cellulose triacetate (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, cycloolefin resins such as polynorbornene, polyolefin resins, (meth)acrylic acid resins, and acetate resins.
[0270] Typically, the optical laminate 20E is disposed on the viewable side of an image display device (e.g., an organic EL display device), and the first protective film 26A is disposed on the viewable side. Therefore, the first protective film 26A can be subjected to surface treatments such as hard coating (HC), anti-reflective treatment, anti-adhesion treatment, and anti-glare treatment as needed.
[0271] The thickness of the first protective film 26A is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and even more preferably 15 μm to 35 μm. It should be noted that, when the above-described surface treatment is performed, the thickness of the first protective film 26A includes the thickness of the surface treatment layer.
[0272] The second protective film 26B can be formed, for example, from any suitable resin film that can be used as a protective layer for the polarizer 25. For the second protective film 26B formed from a resin film, the same explanation as for the first protective film 26A applies. Alternatively, for example, the second protective film 26B can be a solidified or cured layer of a coating film containing an organic solvent solution of resin. By making the second protective film 26B a solidified or cured layer of a coating film containing an organic solvent solution of resin, the adhesion to the polarizer 25 can be improved.
[0273] In one embodiment, the glass transition temperature (Tg) of the resin (base polymer) forming the solidified or cured layer can be 85°C or higher, and the weight-average molecular weight (Mw) can be 25,000 or higher. By setting the Tg and Mw of the resin within such ranges, excellent durability in high-temperature and high-humidity environments can be achieved even with a very thin thickness. The Tg of the resin is preferably 90°C or higher, more preferably 100°C or higher, even more preferably 110°C or higher, and particularly preferably 120°C or higher. The Tg can, for example, be 200°C or lower. Furthermore, the Mw of the resin is preferably 30,000 or higher, more preferably 35,000 or higher, and even more preferably 40,000 or higher. The Mw can, for example, be 150,000 or lower.
[0274] As the resin, any suitable resin can be used as long as it can form a solidified or cured product (e.g., a thermosetting product) of a coating film that can form an organic solvent solution. A thermoplastic or thermosetting resin having the Tg and Mw described above is preferred, and a thermoplastic resin is more preferred. Only one type of resin may be used, or two or more may be used in combination.
[0275] Examples of thermoplastic resins include acrylic resins and epoxy resins. Acrylic resins and epoxy resins can be used in combination.
[0276] Typically, acrylic resins contain repeating units derived from (meth)acrylate monomers having a linear or branched structure as the main component. Acrylic resins may contain repeating units derived from any suitable comonomer corresponding to the purpose. Examples of comonomers include: carboxyl-containing monomers, hydroxyl-containing monomers, amide-containing monomers, aromatic (meth)acrylate monomers, and heterocyclic vinyl monomers. By appropriately setting the type, quantity, combination, and copolymerization ratio of the monomer units, acrylic resins having the given Mw can be obtained. Specific examples of acrylic resins include boron-containing acrylic resins and acrylic resins containing lactone rings, as described in Japanese Patent Application Publication Nos. 2021-117484
[0034] to
[0056] .
[0277] As the epoxy resin, an epoxy resin containing an aromatic ring is preferred. Using an epoxy resin containing an aromatic ring improves the adhesion between the second protective film 26B and the polarizer 25. Furthermore, it enhances the anchoring force of the first adhesive layer 30 adjacent to the second protective film 26B. Examples of epoxy resins containing an aromatic ring include: bisphenol-type epoxy resins such as bisphenol A, bisphenol F, and bisphenol S; phenolic varnish-type epoxy resins such as phenolic varnish epoxy resin, cresol varnish epoxy resin, and hydroxybenzaldehyde phenolic varnish epoxy resin; multifunctional epoxy resins such as glycidyl ether of tetrahydroxyphenylmethane, glycidyl ether of tetrahydroxybenzophenone, and epoxidized polyvinylphenol; naphthol-type epoxy resins; naphthyl-type epoxy resins; and biphenyl-type epoxy resins. Bisphenol A type epoxy resin, biphenyl type epoxy resin, and bisphenol F type epoxy resin are preferred. Only one type of epoxy resin can be used, or two or more types can be used in combination.
[0278] The second protective film 26B can be formed by coating an organic solvent solution of the aforementioned resin to form a coated film, and then allowing the coated film to solidify or be thermally cured. As the organic solvent, any suitable organic solvent capable of dissolving or uniformly dispersing acrylic or epoxy resins can be used. Specific examples of organic solvents include ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone. The resin concentration of the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coated film can be formed.
[0279] The solution can be applied to any suitable substrate or to the polarizer 25. When the solution is applied to a substrate, the solidified or cured coating film (resin layer) formed on the substrate is transferred to the polarizer 25. When the solution is applied to the polarizer 25, the second protective film 26B is directly formed on the polarizer 25 by drying (solidifying) or curing the coating film. It is preferable to apply the solution to the polarizer 25 and form the second protective film 26B directly on the polarizer 25. With this configuration, the adhesive layer or bonding agent layer required for transfer can be omitted, thus further reducing the thickness of the polarizing film 2A. Any suitable method can be used as the solution application method. Specific examples include roller coating, spin coating, wire rod coating, dip coating, mold coating, curtain coating, spray coating, and blade coating (comma-shaped coating, etc.).
[0280] A second protective film 26B can be formed by solidifying or heat-curing the coating film of the solution. The heating temperature for solidification or heat curing is preferably below 100°C, more preferably 50°C to 70°C. If the heating temperature is within this range, adverse effects on the polarizer 25 can be prevented. The heating time can vary depending on the heating temperature. For example, the heating time can be from 1 minute to 10 minutes.
[0281] The second protective film 26B (essentially an organic solvent solution of the aforementioned resin) may contain any suitable additives depending on the purpose. Specific examples of additives include: ultraviolet absorbers; leveling agents; hindered antioxidants such as phenols, phosphorus compounds, and sulfur compounds; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers and carbon fibers; near-infrared absorbers; flame retardants such as tri(dibromopropyl) phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic or inorganic fillers; resin modifiers; organic and inorganic fillers; plasticizers; lubricants; and flame retardants. The type, quantity, combination, and dosage of additives may be appropriately determined according to the purpose.
[0282] In the case of a coagulated or cured layer of a coating film containing an organic solvent solution of resin, the thickness of the second protective film 26B is preferably 0.05 μm to 10 μm, more preferably 0.08 μm to 5 μm, even more preferably 0.1 μm to 1 μm, and particularly preferably 0.2 μm to 0.7 μm.
[0283] The first retardation film 2B may have any suitable optical and / or mechanical properties depending on the purpose. The first retardation film 2B typically has a slow axis. In one embodiment, the angle θ between the slow axis of the first retardation film 2B and the absorption axis of the polarizer 25 is, for example, 40° to 50°, preferably 42° to 48°, and more preferably about 45°. If the angle θ is within such a range, an optical laminate 20E with very excellent circular polarization characteristics (resulting in very excellent anti-reflection characteristics) can be obtained by fabricating the first retardation film 2B as a λ / 4 waveplate.
[0284] The first retardation film 2B preferably exhibits a refractive index characteristic showing a relationship of nx > ny ≥ nz. In one embodiment, the first retardation film 2B can function as a λ / 4 waveplate. In this case, the in-plane phase difference Re(550) of the first retardation film 2B is, for example, 100 nm to 190 nm, preferably 110 nm to 170 nm, and more preferably 130 nm to 160 nm. It should be noted that here, "ny = nz" includes not only the case where ny and nz are exactly equal, but also the case where they are substantially equal. Therefore, without impairing the effects of the present invention, there may be a case where ny < nz.
[0285] The Nz coefficient of the first retardation film 2B is preferably 0.9 to 3, more preferably 0.9 to 2.5, even more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3. By satisfying this relationship, when the resulting optical laminate 20E is used in an image display device, very excellent reflective hue can be achieved.
[0286] The first retardation film 2B can exhibit inverse dispersion wavelength characteristics where the phase difference value increases with the wavelength of the measurement light, positive wavelength dispersion characteristics where the phase difference value decreases with the wavelength of the measurement light, or flat wavelength dispersion characteristics where the phase difference value hardly changes with the wavelength of the measurement light. In one embodiment, the first retardation film 2B exhibits inverse dispersion wavelength characteristics. In this case, the Re(450) / Re(550) of the first retardation film 2B is, for example, 0.8 or more and less than 1, preferably 0.8 or more and less than 0.95. With such a configuration, very excellent anti-reflection characteristics can be achieved.
[0287] The first phase retardation film 2B preferably has an absolute value of 2 × 10⁻⁶ for its photoelastic coefficient.-11 m 2 / N or less, more preferably 2.0×10 -13 m 2 / N~1.5×10 -11 m 2 / N, further preferably 1.0×10 -12 m 2 / N~1.2×10 -11 m 2 / N resin. If the absolute value of the photoelastic coefficient is within such a range, the phase difference is less likely to change under shrinkage stress generated during heating. As a result, thermal unevenness in the resulting image display device can be well prevented.
[0288] The first retardation film 2B is typically composed of a stretched film of a resin film. The thickness of the first retardation film 2B is, for example, 70 μm or less, preferably 60 μm or less, more preferably 10 μm to 50 μm, and even more preferably 20 μm to 45 μm. If the thickness of the first retardation film 2B is within such a range, good flexibility can be ensured, making it suitable for flexible applications.
[0289] The first retardation film 2B can be composed of any suitable resin film capable of satisfying the above-described characteristics. Representative examples of such resins include polycarbonate resins, polyester carbonate resins, polyester resins, polyvinyl acetal resins, polyarylate resins, cyclic olefin resins, cellulose resins, polyvinyl alcohol resins, polyamide resins, polyimide resins, polyether resins, polystyrene resins, and acrylic resins. These resins can be used alone or in combination (e.g., blending, copolymerization). When the first retardation film 2B is composed of a resin film exhibiting inverse dispersion wavelength characteristics, polycarbonate resins or polyester carbonate resins (hereinafter sometimes simply referred to as polycarbonate resins) can be suitably used.
[0290] As the aforementioned polycarbonate resin, any suitable polycarbonate resin can be used as long as the effects of the present invention are achieved. For example, the polycarbonate resin comprises structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, and structural units derived from at least one dihydroxy compound selected from alicyclic diols, alicyclic diethanols, di-, tri-, or polyethylene glycols, and alkylene diols or spirodiols. Preferably, the polycarbonate resin comprises structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, structural units derived from alicyclic diethanols, and / or structural units derived from di-, tri-, or polyethylene glycols; more preferably, it comprises structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, and structural units derived from di-, tri-, or polyethylene glycols. The polycarbonate resin may, as needed, comprise structural units derived from other dihydroxy compounds. It should be noted that details of the polycarbonate resin suitable for use in the first retardation film 2B and the method for forming the first retardation film 2B are described, for example, in Japanese Patent Application Publication Nos. 2014-10291, 2014-26266, 2015-212816, 2015-212817, and 2015-212818, and these publications are incorporated herein by reference.
[0291] In one embodiment, by contacting the second adhesive layer 35 side surface of the first retardation film 2B with an organic solvent and then providing the second adhesive layer 35 on the contact surface, a compatibility region in which the composition continuously changes towards the second adhesive layer 35 side can be formed on the first retardation film 2B. By forming a compatibility region in which the constituent components of the first retardation film 2B and the constituent components of the second adhesive layer 35 are compatible, the adhesion between the first retardation film 2B and the second retardation film 2C can be improved. On the other hand, from the viewpoint of strictly suppressing moisture penetration into the first retardation film 2B, it is preferable not to provide a compatibility region. Therefore, it is preferable to form a compatibility region as needed, taking into account the adhesion between the first retardation film 2B and the second retardation film 2C, the application of the optical laminate 20E, or the usage environment. Details of the method for forming the compatibility region are described in Japanese Patent Application Publication No. 2019-56820, which is incorporated herein by reference.
[0292] The second retardation film 2C can be a so-called positive C-plate whose refractive index characteristics show a relationship of nz > nx = ny. By using a positive C-plate as the second retardation film 2C, oblique reflections can be effectively prevented, and a wide viewing angle can be achieved for anti-reflection function.
[0293] The phase difference Rth(550) in the thickness direction of the second phase retardation film 2C is preferably -50nm to -300nm, more preferably -70nm to -250nm, even more preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. Here, "nx = ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane phase difference Re(550) of the second phase retardation film 2C can be less than 10nm.
[0294] The second retardation film 2C, having a refractive index characteristic of nz > nx = ny, can be formed from any suitable material. The second retardation film 2C is preferably composed of a film containing a liquid crystal material fixed in a vertical orientation. The liquid crystal material (liquid crystal compound) capable of vertical orientation can be a liquid crystal monomer or a liquid crystal polymer. As a specific example of the liquid crystal compound and the method for forming the second retardation film 2C, the method for forming the liquid crystal compound and retardation layer described in Japanese Patent Application Publication Nos. 2002-333642
[0020] to
[0028] can be cited. In this case, the thickness of the second retardation film 2C is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0295] As the adhesive constituting the first adhesive layer 30 and the second adhesive layer 35, any suitable adhesive can be used. Examples of adhesives include those described above for the optical laminate 20A.
[0296] An optical laminate can have any configuration as long as it has an adhesive sheet 1 and an optical film 2.
[0297] The adhesive sheet 1 can be disposed between any layers of the optical laminate. In other words, the adhesive sheet 1 can be a so-called interlayer adhesive layer.
[0298] The optical laminates of the embodiments of the present invention can be distributed and stored, for example, in the form of a wound body formed by winding a strip of optical laminates, or in the form of a single sheet of optical laminates.
[0299] Typically, the optical laminates of embodiments of the present invention can be used in image display devices. Image display devices are, for example, EL displays such as liquid crystal displays, organic EL displays, and inorganic EL displays.
[0300] 4. Image Display Devices
[0301] An example of an image display device according to an embodiment of the present invention is shown below. Figure 8 . Figure 8The image display device 21 has a stacked structure in which a substrate 7, an image forming layer (e.g., an organic EL layer or a liquid crystal layer) 6, an adhesive sheet 4, a phase retardation film 2B, an adhesive sheet 1, a polarizing film 2A, and a protective film 5 are sequentially stacked. Figure 6 The optical laminate 20D (excluding the release liner 3). The image display device 21 may also have Figures 3-5 Optical laminate 20D can be replaced by optical laminates 20A, 20B, 20C, and 20E. The substrate 7 and the image forming layer 6 can have the same configuration as those of the substrate and image forming layer in a known image display device.
[0302] Figure 8 The image display device 21 can be an organic EL display or a liquid crystal display. However, the image display device 21 is not limited to this example. The image display device 21 can also be an electroluminescent (EL) display, a plasma display (PD), a field emission display (FED), etc. The image display device 21 can be used for home appliances, automotive applications, public information displays (PIDs), etc.
[0303] The image display device 21 can have any configuration as long as it has the adhesive sheet 1 and / or the optical laminate 20.
[0304] Example
[0305] The present invention will be specifically described below through embodiments, but the present invention is not limited to these embodiments in any way.
[0306] [Synthesis of dispersants]
[0307] 415 g (1 mol) of tristyrene phenol and 1 g (0.018 mol) of potassium hydroxide were added to an autoclave and mixed uniformly until the reaction system reached 130 °C. Then, 352 g (8 mol) of ethylene oxide (EO) was added dropwise. After the addition was complete, the pressure was maintained at 0.1 MPa at 130 °C for 1 hour to obtain the EO 8-molar adduct of tristyrene phenol. Next, 767 g (1 mol) of the obtained EO 8-molar adduct of tristyrene phenol and 152 g (1.3 mol) of sodium monochloroacetate were added to a reactor and stirred until homogeneous. The reaction system was then brought to 60 °C, 52 g of sodium hydroxide was added, and the temperature was raised to 80 °C for 3 hours. After aging, the mixture was cooled to 50 °C, and 117 g (1.2 mol) of 98% sulfuric acid was added dropwise at the same temperature to obtain a white suspension. The suspension was washed with distilled water, and the solvent was removed by vacuum distillation to obtain the dispersant.
[0308] [Preparation of Zirconia Dispersion]
[0309] A mixture was prepared by adding 1.5 parts by weight of the dispersant prepared above and 28.5 parts by weight of phenoxybenzyl acrylate (Kyoei Chemical Industry, trade name "LIGHT ACRYLATEPOB-A"; hereinafter referred to as "POB-A") to 100 parts by weight of a methanol dispersion of zirconia particles (manufactured by SAKAI CHEMICAL INDUSTRY, grade "SZR-M", average particle size (D50) based on dynamic light scattering method: 3 nm, zirconia particle concentration: 30 wt%). The solvent was then removed under reduced pressure using a rotary evaporator to obtain a dispersion of zirconia particles. The resulting dispersion contained zirconia particles / dispersant / POB-A in a weight ratio of 50 / 2.5 / 47.5.
[0310] [Preparation of Polymer B]
[0311] In a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet tube, and condenser, 99 parts by weight of POB-A, 1 part by weight of 4-hydroxybutyl acrylate (4HBA), 0.30 parts by weight of 2,2'-azobisisobutyronitrile (2,2'-azobisisobutyronitrile) as a polymerization initiator, 3 parts by weight of 1-thioglycerol as a chain transfer agent, and 300 parts by weight of ethyl acetate were added. The mixture was kept at 70°C and nitrogen was slowly introduced while stirring to allow for nitrogen purging for at least 1 hour. The liquid temperature in the flask was then maintained at 72–74°C for 6 hours to prepare a polymer B solution. Next, the solution was heated at 90°C for 12 hours, followed by vacuum treatment at 120°C for 3 hours to remove the ethyl acetate. Thus, polymer B (weight-average molecular weight 4000) with less than 0.1 parts by weight of ethyl acetate as detected by gas chromatography was obtained.
[0312] [Weight-average molecular weight of polymer B]
[0313] The weight-average molecular weight (Mw) of polymer B was determined by GPC (gel permeation chromatography). The apparatus and conditions were set as described below.
[0314] • Analytical apparatus: Waters, Alliance
[0315] • Chromatographic column: Tosoh, TSKgel SuperHZM-H × 2 columns
[0316] Column temperature: 40℃
[0317] • Elution buffer: THF
[0318] • Flow rate: 0.2 mL / min
[0319] Injection volume: 30μL
[0320] • Detector: Differential refractive index detector (RI)
[0321] • Standard sample: Agilent, polystyrene (PS)
[0322] [Preparation of Adhesive Composition A1]
[0323] The zirconia dispersion prepared above was mixed with phenoxybenzyl acrylate (POB-A) and 4-hydroxybutyl acrylate (4HBA). The amount of zirconia dispersion was set such that the weight of zirconia particles relative to the total weight of POB-A (the sum of POB-A contained in the zirconia dispersion and POB-A mixed in the zirconia dispersion) and 4HBA, i.e., the weight of monomer component M, was 81.8 parts by weight per 100 parts by weight. The weight ratio of POB-A, 4HBA, and zirconia particles was 50 / 5 / 45, and the weight ratio of monomer component M and zirconia particles was 55 / 45. The proportion of POB-A in monomer component M was 90.9% by weight, and the proportion of 4HBA was 9.1% by weight. Next, relative to 100 parts by weight of the above mixture, 0.4 parts by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad 819, manufactured by IGM Resins) as a photopolymerization initiator, 1.25 parts by weight of Tinuvin 571 (manufactured by BASF) as UVA, 0.025 parts by weight of 1,9-nonanediol diacrylate (NDDA) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 10 parts by weight of the polymer B prepared above were mixed. Next, the mixture in the flask was irradiated with ultraviolet light under a nitrogen atmosphere, thereby obtaining a photocurable adhesive composition A1 in which monomer component M partially underwent photopolymerization. The ultraviolet irradiation was continued until the viscosity of the liquid in the flask (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached approximately 20 Pa·s.
[0324] [Preparation of adhesive compositions A2~A22]
[0325] The types and amounts of monomers, the types and amounts of photopolymerization initiators, the types and amounts of UVA, and the presence or absence of zirconia dispersion were changed as described in Table 1. Otherwise, photocurable adhesive compositions A2 to A22 were prepared by the same method as adhesive composition A1.
[0326]
[0327] The abbreviations in Table 1 are as follows.
[0328] (monomer)
[0329] •POB-A: Phenoxybenzyl acrylate
[0330] ·OPPE: o-Phenylphenol acrylate
[0331] PEA: Phenoxyethyl acrylate
[0332] 4HBA: 4-Hydroxybutyl acrylate
[0333] ·BA: n-Butyl acrylate
[0334] (Photopolymerization initiator)
[0335] Omnirad 819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resins; prepared at a concentration of 1×10⁻⁶). -4 The absorbance of a g / mL acetonitrile solution to light at a wavelength of 370 nm is 3 × 10⁻⁶ g / mL. -2 above)
[0336] Omnirad 651: 2,2-Dimethoxy-1,2-diphenylethane-1-one (manufactured by IGM Resins; prepared to a concentration of 1×10⁻⁶). -4 The absorbance of a g / mL acetonitrile solution at a wavelength of 370 nm is less than 3 × 10 g / mL. -2 )
[0337] (UVA)
[0338] Tinuvin 571 (manufactured by BASF; benzotriazole, liquid at 25°C)
[0339] Tinuvin 928 (manufactured by BASF; benzotriazole, powder at 25°C)
[0340] Tinuvin 384-2 (manufactured by BASF; benzotriazole, liquid at 25°C)
[0341] Tinuvin 405 (manufactured by BASF; triazine derivative, powder at 25°C)
[0342] • Tinosorb S (manufactured by BASF; triazine derivative, powder at 25°C)
[0343] (Example 1)
[0344] [Making of the peelable liner]
[0345] A silicone-based release agent composition was prepared by mixing 30 parts by weight of an addition-reaction curable silicone (containing LTC761 with hexenyl polysiloxane, 30% toluene solution, manufactured by Toray Dow Corning), 0.9 parts by weight of a release control agent (containing unreactive silicone resin BY24-850, manufactured by Toray Dow Corning), 2 parts by weight of a curing catalyst (containing platinum catalyst SRX212, manufactured by Toray Dow Corning), and a toluene / hexane mixed solvent (volume ratio 1:1) as a diluent. The concentration of the silicone solid component in the release agent composition was 1.0% by weight. Next, the release agent composition was coated onto one side of a substrate (Lumirror XD500P polyester film, 75 μm thick) using a wire rod, and heated at 130°C for 1 minute to produce a release liner with a release layer (60 nm thick) on one side.
[0346] [Making the Adhesive Sheet]
[0347] Adhesive composition A1 was applied to the release liner, which was prepared as a substrate sheet, using an applicator to form a coating layer. The coating layer was formed on the release layer. Next, the release liner was placed on the formed coating layer to obtain a first laminate. The release liner was configured such that the release layer and the coating layer were in contact. Next, at an illuminance of 2.5 mW / cm²... 2 And cumulative light intensity 2400mJ / cm 2 Under conditions of seconds, ultraviolet light from a black light source is irradiated from one side of the substrate sheet of the first laminate (first step irradiation). Next, under an illuminance of 18 mW / cm²... 2 And cumulative light intensity 17280mJ / cm 2 Under certain conditions, ultraviolet light from a metal halide was irradiated from one side of the substrate sheet of the first laminate (second irradiation). This caused the coating layer to photocur, resulting in the adhesive sheet (50 μm thick) of Example 1, held between the substrate sheet and the release liner. It should be noted that the illuminance was measured using an illuminance meter (TOPCON TECHNOHOUSE, UD-T36T2) near the incident surface of the ultraviolet light on the substrate sheet.
[0348] (Examples 2-21 and Comparative Example 1)
[0349] The adhesive composition used was modified as shown in Table 2. Otherwise, adhesive sheets of Examples 2-21 and Comparative Example 1 were obtained by the same method as in Example 1.
[0350]
[0351] [evaluate]
[0352] (Refractive index of the adhesive sheet)
[0353] For each adhesive sheet of the examples and comparative examples, the refractive index of the surface exposed by peeling off the release liner was measured using a prism coupler (manufactured by Metricon Co., Ltd., model "2010M") in critical angle mode at a measurement temperature of 25°C and a measurement wavelength of 594nm.
[0354] (Lightfastness Test 1: Peeling)
[0355] For each adhesive sheet in the examples and comparative examples, test sheets were prepared by bonding an alkali-free glass plate (thickness 0.7~0.8 mm, total light transmittance 92%, haze 0.06%) to each surface exposed by peeling off the substrate sheet and release liner. The test sheets were placed in a Super Xenon Lamp Weathering Tester SX75 (Suga Test Instruments Co., Ltd.) capable of conducting accelerated sunlight irradiation tests at an irradiance of 120 W / m² at 300-400 nm. 2 A 500-hour lightfastness test was conducted at 30°C. The test pieces were visually inspected after the test, and the peeling condition of the adhesive sheet relative to the glass plate was evaluated according to the following criteria.
[0356] A: Overall, no stripping was confirmed, which is excellent.
[0357] B: Minor peeling was observed at the periphery, but the condition was good.
[0358] C: Although peeling was observed, it was at a level that did not pose a problem in use.
[0359] D: Observation of the level of peeling that becomes a problem in use depending on the purpose and size of the image display device.
[0360] (Lightfastness Test 2: Foaming)
[0361] The lightfastness test was performed in the same manner as lightfastness test 1. The test pieces were visually inspected after the test, and the foaming state of the adhesive sheet was evaluated according to the following criteria.
[0362] A: Overall, no foaming was confirmed, which is excellent.
[0363] B: A small amount of foaming was observed, but it was good.
[0364] C: Although foaming was observed, it was at a level that did not pose any problems in use.
[0365] D: Observation of foaming levels that cause problems in use depending on the application and the size of the image display device.
[0366] (Haze)
[0367] For each adhesive sheet in the examples and comparative examples, test sheets were prepared by bonding an alkali-free glass plate (thickness 0.7~0.8 mm, total light transmittance 92%, haze 0.06%) to each exposed surface after peeling off the substrate sheet and release liner. The test sheets were placed in an environment of 23°C and 50%RH for 30 minutes, then subjected to autoclaving at 50°C and 0.5 MPa for 30 minutes. Next, they were placed in an atmosphere of 23°C and 50%RH for 24 hours. Finally, the haze of the test sheets was measured using a haze meter (Murakami Color Technology Research Institute, HM-150) in a measurement environment of 23°C.
[0368] (color) and light transmittance)
[0369] For each adhesive sheet in the embodiments and comparative examples, an alkali-free glass plate (thickness 0.7~0.8mm, total light transmittance 92%, chromaticity) is bonded to each surface exposed after peeling off the substrate sheet and release liner. A test piece was prepared using 0.20 g of a certain compound. After being placed in an environment of 23°C and 50%RH for 30 minutes, the test piece was placed in a pressure degassing apparatus (autoclave) and subjected to autoclaving at 50°C and 0.5 MPa for 30 minutes. Next, it was placed in an atmosphere of 23°C and 50%RH for 24 hours. Then, the transmittance of the test piece for light with wavelengths from 300 nm to 800 nm was measured using a UV-Vis-NIR spectrophotometer (Hitachi High-Tech, UH4150) at 23°C. Furthermore, the chromaticity was calculated using a color calculation program (Hitachi High-Tech, UV Solutions) based on the obtained spectral data. .
[0370] (Residual amount of photopolymerization initiator)
[0371] For each adhesive sheet of the examples and comparative examples, its composition was analyzed, and the residual amount (content) of the photopolymerization initiator was calculated based on the results. It should be noted that the composition analysis was performed using liquid chromatography (LC) under the following conditions.
[0372] • Device used: 1290 Infinity II (manufactured by Agilent Technologies)
[0373] • Column: Acquity UPLC BEH C18 (Waters, 2.1 mm) (×100mm, 1.7μm)
[0374] • Eluent composition: Gradient conditions of ultrapure water / acetonitrile
[0375] Column temperature: 40℃
[0376] • Column flow rate: 0.2 mL / min
[0377] Injection volume: 2μL
[0378] • Detector: Photodiode Array Detector (PDA)
[0379] • Measurement wavelength: 190~400nm
[0380] • Extraction wavelengths: Omnirad 651 = 253nm, Omnirad 819 = 296nm
[0381] • Sample preparation method: Weigh approximately 0.5 g of the sample (adhesive sheet), add 2 mL of chloroform and shake overnight. Add 8 mL of methanol to the resulting solution, and filter the supernatant using a 0.45 μm membrane filter. Inject the filtrate into an LC filter for analysis.
[0382] (Adhesive sheet storage test)
[0383] Each adhesive sheet of the embodiment was kept in a constant temperature and humidity bath at 20°C and 98%RH for 30 days while still bonded with the substrate sheet and the release liner. The presence or absence of crystalline precipitates in the adhesive sheets was confirmed, and the state of the precipitates was evaluated according to the following criteria.
[0384] A: No crystallization was observed.
[0385] B: The precipitation of a small amount of crystals of a size that could not be confirmed by the naked eye was observed.
[0386] C: Observation of crystallization at levels that cause problems in use depending on the application and the size of the image display device.
[0387] The evaluation results are shown in Table 3 below.
[0388]
[0389] As shown in Table 3, compared with the comparative example, the degree of peeling during the lightfastness test was suppressed in each adhesive sheet of the embodiment.
[0390] Industrial applicability
[0391] The adhesive sheet formed from the adhesive composition of the present invention can be used in image display devices such as EL displays and liquid crystal displays.
Claims
1. An adhesive composition comprising at least one selected from monomeric component M and its polymers, The monomeric component M comprises monomer a having a double-bonded ring. The adhesive composition contains an ultraviolet absorber. The adhesive sheet formed from the adhesive composition has a refractive index of 1.55 or higher.
2. The adhesive composition according to claim 1, wherein, The double-bonded ring is an aromatic ring.
3. The adhesive composition according to claim 1, wherein, The monomer a comprises a (meth)acrylic acid monomer having the double-bonded ring.
4. The adhesive composition according to claim 1, wherein, The monomer a contains phenoxybenzyl acrylate.
5. The adhesive composition according to claim 1, wherein, The content of monomer a in the monomer component M is more than 30% by weight.
6. The adhesive composition according to claim 1, wherein, The ultraviolet absorber is liquid at 25°C.
7. The adhesive composition according to claim 1, wherein, The haze of the adhesive sheet is below 2.0%.
8. The adhesive composition according to claim 1, wherein, The transmittance of the adhesive sheet in the thickness direction is less than 25% for light with a wavelength of 380nm and more than 80% for light with a wavelength of 420nm.
9. The adhesive composition according to claim 1, wherein, The colorimetric properties of the adhesive sheet conform to CIE 1976 L as specified in JIS Z8781-4:2013. ,a ,b Color saturation in a color space The absolute value is represented as below 2.
0.
10. The adhesive composition according to claim 1, wherein, The adhesive composition is a photocurable adhesive composition containing a photopolymerization initiator.
11. The adhesive composition according to claim 10, wherein, The photopolymerization initiator is prepared at a concentration of 1×10⁻⁶. -4 The absorbance of a g / mL acetonitrile solution to light at a wavelength of 370 nm is 3 × 10⁻⁶ g / mL. -2 above.
12. The adhesive composition according to claim 10, wherein, The residual amount of the photopolymerization initiator in the adhesive sheet is less than 200 ppm (by weight).
13. The adhesive composition according to claim 1, further comprising inorganic particles.
14. An adhesive sheet formed from the adhesive composition according to any one of claims 1 to 13.
15. An optical laminate comprising: The adhesive sheet as described in claim 14, and Optical film.
16. An image display device comprising the optical laminate of claim 15.
Citation Information
Patent Citations
Optically active liquid crystal compound having cyano group
JP1989070455A
Homeotropic alignment liquid-crystalline composition, method for producing homeotropic alignment liquid crystal film and homeotropic alignment liquid crystal film
JP2002333642A
Draining device, and indoor unit of air conditioner
JP2012013303A
Manufacturing method of thin polarizing film
JP2012073580A
Optical display device having polarizing film
JP2012133303A